Sealing sheet, and display with resin composition layer
Patent Information
- Application Number
- JP2024075618
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2023-08-23
- Filing Date
- 2024-05-08
- Publication Date
- 2025-03-07
AI Technical Summary
【0008】 本開示により、光半導体素子の埋め込み性に優れ、特にマイクロLED素子を光源とするディスプレイに適用した場合においても、埋め込み性とシームレス性、密着性と視認性に優れる封止シート及び樹脂組成物層を有するディスプレイを提供することが可能となった。
Smart Images

Figure 2025031514000001_ABST
Abstract
Description
[Technical field]
[0001] The present disclosure relates to an encapsulating sheet, and more particularly to an encapsulating sheet including a resin composition layer for encapsulating an optical semiconductor element used in various products including, for example, electronic devices and displays, and a display equipped with the resin composition layer. [Background technology]
[0002] In recent years, displays have been actively developed using various light-emitting elements in order to achieve higher performance. Specifically, various display specifications are being researched, such as backlit displays using liquid crystal or quantum dots, displays using self-emitting elements such as mini / micro LEDs and organic EL, plasma displays, and electrophoretic displays, and a wide range of uses are being considered, from large display applications such as signage and televisions to small-sized devices such as tablets, personal computers, smartphones, and wearable devices. In particular, the development of displays using LEDs is progressing day by day, and Patent Document 1 describes a thermosetting resin composition that encapsulates LED elements. Micro LED displays are attracting the most attention as a next-generation display technology. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] International Publication No. 2021 / 200035 Summary of the Invention [Problem to be solved by the invention]
[0004] Patent Document 1 describes a sheet for encapsulating optical semiconductor elements that is easy to handle and can encapsulate optical semiconductor elements in a simple process and in a short time. However, in optical semiconductor elements that have been getting smaller in recent years, the spacing between the optical semiconductor elements has become narrower, making it difficult for the sheet-like resin composition described in Patent Document 1 to conform to the micro-sized optical semiconductor elements and fill the gaps (embedding properties). When there is a gap between the optical semiconductor element and the encapsulating resin composition, particularly in an LED display module, the brightness decreases due to light refraction in the gap. In addition, micro LED displays are made by connecting small micro LED display modules of about 9 to 10 inches vertically and horizontally in a tiled pattern to create a large screen. In this case, there is a problem that the seams of the modules are noticeable (seamlessness) when the display is viewed from a close distance. In addition to high brightness, there is a demand for encapsulating sheets that have excellent embeddability and seamlessness in order to create displays with inconspicuous seams.
[0005] The present disclosure has been made in view of the above problems, and aims to provide an encapsulating sheet having excellent embeddability for optical semiconductor elements. In addition, an object of the present disclosure is to provide an encapsulating sheet and a display having a resin composition layer having excellent embeddability, seamlessness, and visibility, particularly when applied to a display using a micro LED element as a light source. Another object of the present invention is to provide an encapsulating sheet having excellent adhesion to a substrate from the viewpoint of simplifying the manufacturing process of a micro LED display. [Means for solving the problem]
[0006] As a result of extensive investigations, the present inventors have found that the above problems can be solved by the light-shielding sheet described below, and have completed the present inventions [1] to [9] below.
[0007] [1]: An encapsulating sheet for encapsulating an optical semiconductor element, the encapsulating sheet comprising a protective film and a resin composition layer arranged in this order, the resin composition layer containing a resin (A) and metal oxide particles (B), the metal oxide particles (B) having a number-average primary particle diameter of 5 to 50 nm, and the resin composition layer having a refractive index of 1.45 to 1.65. [2]: The encapsulating sheet according to [1], wherein the metal oxide particles (B) contain at least one selected from the group consisting of Ti, Al, and Zr. [3]: The encapsulating sheet according to [1], wherein the resin (A) includes at least one resin selected from the group consisting of a (meth)acrylic resin (a) and a urethane resin (b). [4]: The resin composition layer has a haze of 12% or less and a total light transmittance of 80% or more, and the CIE L * a * b * The encapsulating sheet according to [1], wherein the chroma C* calculated from a color space is 0 to 10. [5]: The encapsulating sheet according to [1], wherein the resin composition layer has a thickness Ta of 1 to 100 μm, and the protective film has a thickness Tb of 10 to 188 μm. [6]: The encapsulating sheet according to [5], wherein the protective film and the resin composition layer are directly laminated to each other, and the ratio of the root-mean-square height Sq defined in ISO 25178 on the surface of the protective film in contact with the resin composition layer to the thickness Ta of the resin composition layer is 0.01 to 30%. [7]: The encapsulating sheet according to any one of [1] to [6], wherein the loss tangent of the resin composition layer obtained by dynamic viscoelasticity measurement has a peak top intensity (tan δ peak intensity) of 0.6 to 2.2 in the range of −50 to 80° C. [8]: The encapsulating sheet according to [7], wherein the optical semiconductor element is a micro LED. [9]: A display having a sealing layer containing a resin (A) and metal oxide particles (B), wherein the metal oxide particles (B) have a number average primary particle diameter of 5 to 50 nm and a refractive index of 1.45 to 1.65. Effect of the Invention
[0008] According to the present disclosure, it has become possible to provide a display having an encapsulating sheet and a resin composition layer which are excellent in embeddability of optical semiconductor elements, and which are excellent in embeddability, seamlessness, adhesion and visibility, particularly when applied to a display using a micro LED element as a light source. [Brief description of the drawings]
[0009] [Figure 1] FIG. 2 is a schematic cross-sectional view showing an example of a laminate configuration of an encapsulating sheet. [Diagram 2] 1A to 1C are schematic cross-sectional views showing a step of forming a sealing layer over a substrate having an optical semiconductor element. [Diagram 3] FIG. 1 is a cross-sectional view showing an example of a test substrate simulating a micro LED substrate. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0010] The present disclosure will be described in detail below. Note that the embodiment described below is an example of the present disclosure. The present disclosure is not limited to the following embodiment, and includes modified examples that are implemented within the scope of the present disclosure. In this specification, a numerical range specified by using "~" includes the numerical values before and after "~" as the lower and upper limit ranges. (Meth)acrylic acid refers to acrylic acid and methacrylic acid. In addition, unless otherwise noted, each of the various components appearing in this specification may be used independently, either alone or in combination of two or more.
[0011] [Form of encapsulating sheet] As shown in Fig. 1(a), the encapsulating sheet of the present disclosure includes a resin composition layer 2 and a protective film 3 arranged in this order. A plurality of resin composition layers 2 may be provided. is preferably laminated directly on the resin composition layer.
[0012] The protective film is a support for the resin composition layer and provides handleability to the encapsulating sheet. The protective film is preferably used in such a manner that it is peeled off after the encapsulating layer is formed around the optical semiconductor element by the resin composition layer.
[0013] In the above-mentioned usage form, the protective film is not particularly limited, and examples thereof include polyester films such as polybutylene terephthalate and polyethylene naphthalate, polyolefin films such as polypropylene and polyethylene, polyvinyl chloride films, polyurethane films, nylon films, polyolefin films, triacetyl cellulose films, and cycloolefin films. The plastic film preferably has a releasing property, and more preferably has a release layer formed by applying a release agent such as silicone resin, alkyd resin, fluororesin, or melamine resin to the plastic film. The plastic film may have a functional layer in addition to the release layer, specifically, examples of the functional layer include antistatic layer / plastic film substrate / release layer and plastic film substrate / antistatic layer / release layer.
[0014] The thickness Tb of the protective film (including the thickness of the release layer if a release layer is provided) is not particularly limited, but is preferably 10 to 188 μm, more preferably 10 to 100 μm, and even more preferably 10 to 75 μm. By setting it within the above range, the transfer of the undulations of the protective film to the resin composition layer is controlled, and the embedding property and adhesion are improved. The thickness Tb can be measured, for example, by the method described in the examples below.
[0015] When the protective film is directly laminated with the resin composition layer, the ratio of the root mean square height Sq of the surface roughness according to ISO 25178 to the thickness Ta of the resin composition layer is preferably 0.01 to 30%, more preferably 0.1 to 20%, and even more preferably 0.15 to 12% on the surface of the protective film in contact with the resin composition layer. By setting it in the above range, the surface roughness transferred to the resin composition layer is controlled, and the resin composition layer is sufficiently smoothed in the pressing process described later, thereby improving seamlessness and adhesion. The root mean square height Sq can be measured, for example, by the method described in the examples described later. The root mean square height Sq value is preferably from 0.01 to 2 μm, more preferably from 0.04 to 1.5 μm, and even more preferably from 0.1 to 1.5 μm.
[0016] The root mean square height Sq can be adjusted by the release treatment of the release layer surface of the protective film. For example, it can be adjusted by the type of release agent, the amount of release agent applied, and the method of applying the release agent. If the value of the root mean square height Sq is to be increased, it is effective to reduce the amount of release agent applied, speed up the drying after the release agent is applied, or make the release agent contain a filler, and if the value of the root mean square height Sq is to be decreased, it is only necessary to adjust it in the opposite manner. In addition, a method of transferring unevenness using a film or carrier material having a predetermined root mean square height Sq can also be applied.
[0017] The encapsulating sheet of the present disclosure more preferably has a three-layer structure of protective film 3 / resin composition layer 2 / release liner 4 as shown in FIG. 1(b). The release liner is a film in which a release layer is laminated on a substrate, and the substrate and release agent described for the protective film can be used. The release liner and the protective film may be the same, but from the viewpoint of handling, it is preferable to design the release liner 4 so that the release force is smaller than that of the protective film. The peel strength between the protective film 3 and the release liner 4 is determined by the adhesion surface of each release liner to the resin composition layer. It can be adjusted by the release treatment. For example, it can be adjusted by the type of release agent, the coating amount of the release agent, and the surface roughness of the release layer. When it is desired to reduce the value of the release force, treatments such as increasing the coating amount of the release agent are effective. When it is desired to increase the value of the release force, the opposite adjustment can be made. The thickness Tc of the release liner 4 is preferably in the range of 10 to 150 μm, and it is preferable to satisfy the relationship of Tc < Tb. When taking the three-layer structure shown in Fig. 1(b), a manufacturing method in which the resin composition layer 2 is formed on the protective film 3 and then the release liner 4 is laminated is preferable.
[0018] After manufacturing the sealing sheet or while manufacturing the sealing sheet, a sealing sheet roll can be obtained by winding the sealing sheet around a winding core in a roll shape. The winding length can be designed according to the application. From the viewpoint of improving productivity, it is preferably 50 m or more, and more preferably 100 m or more. The winding length is preferably 10,000 m or less from the viewpoint of manufacturing yield. When the sealing sheet is in a roll form, it is preferable to provide the release liner on the outer side of the roll.
[0019] The sealing sheet of the present disclosure is used for sealing an optical semiconductor element. The resin composition layer is preferably directly adhered to the optical semiconductor element for sealing. The optical semiconductor element is not particularly limited, but is preferably disposed on a substrate such as acrylic, urethane, polycarbonate, epoxy, polyimide, glass, paper, cloth, aluminum, ceramic, or polyethylene terephthalate, and preferably has an electrode portion. The optical semiconductor elements are arranged singly or in plurality. When a plurality of optical semiconductor elements are arranged, a light-shielding layer may be provided between the optical semiconductor element portions.
[0020] Since the resin composition layer has high conformability to uneven surfaces, it is suitable to use the resin composition layer by following the optical semiconductor element and filling the gap between the optical semiconductor element. By filling the gap between the optical semiconductor elements with the resin composition layer, an encapsulation layer made of the resin composition layer is formed. The encapsulation layer has a function of fixing the adjacent optical semiconductor elements and preventing them from falling off or becoming biased. In particular, since the resin composition layer of the encapsulation sheet of the present disclosure can conform to the micro-sized optical semiconductor element, a micro LED is more suitable as the optical semiconductor element, and it is even more preferable to use the resin composition layer as the encapsulation layer of a micro LED display panel. Micro LEDs are tiny LED elements (chips) of 50μm or less than 100μm in size. By mounting multiple micro LEDs (chips) on a substrate with wiring and circuits, a display is formed that uses multiple optical semiconductor elements as light sources. Micro LEDs are made up of GaAs, GaP, AlGaInP, InGaN or other LED elements, sealing resin to seal them, package substrate, electrodes, etc., and have an operating temperature of 25 to 60°C. An example of a process for forming a sealing layer will be described below with reference to FIG.
[0021] Step (a): Step of placing the encapsulating sheet As shown in Fig. 2(a), the resin composition layer of the encapsulating sheet is placed on the substrate having the optical semiconductor element so as to directly cover the optical semiconductor element. If the encapsulating sheet has a release liner, the release liner is peeled off to expose the resin composition layer, and then the encapsulating sheet is placed as described above. The protective film may be peeled off immediately after placement, or may be peeled off after the pressing step described below. In this specification, the number of optical semiconductor elements is not particularly limited. In display applications, the number of optical semiconductor elements used is determined by the display size and the number of pixels. Furthermore, the light emission color of the optical semiconductor element is not particularly limited, and examples of colors that can be emitted include red, green, and blue. The optical semiconductor element has a thickness of 100 μm or less and a planar area of 40,000 μm. 2 Below The following is preferable: a thickness of 50 μm or less, and a planar area of 10,000 μm 2 The following is more preferable: a thickness of 20 μm or less, and a planar area of 2,500 μm 2 The following are even more preferred: The distance between the optical semiconductor elements mounted on the substrate is, for example, 10 to 5,000 μm. When a set of red, green, and blue optical semiconductor elements is mounted on the substrate as one pixel, the distance between the pixels is, for example, 10 to 2,000 μm, preferably 20 to 1,800 μm, and more preferably 500 to 1,500 μm. The distance between the optical semiconductor elements in one pixel is, for example, 10 to 200 μm, preferably 10 to 100 μm, and more preferably 20 to 60 μm.
[0022] Process (b): Pressing process As shown in Fig. 2(b), the resin composition layer is fluidized by pressing and filled around the optical semiconductor element and between the optical semiconductor elements. The resin composition layer filled around the optical semiconductor element and between the optical semiconductor elements becomes a sealing layer. The pressing method is not particularly limited, but heat pressing and vacuum pressing are preferred. From the viewpoint of the filling property of the resin composition layer, the temperature during pressing is preferably 20 to 200°C, more preferably 30 to 150°C, further preferably 40 to 130°C, and most preferably 60 to 110°C. In order to improve the adhesion to the optical semiconductor element or the adherend, heat aging may be further performed after pressing. The heating temperature is preferably 40 to 250°C, more preferably 80 to 220°C, and even more preferably 100 to 190°C. The heating time is preferably 30 to 300 minutes, more preferably 60 to 240 minutes, and even more preferably 90 to 180 minutes. By setting the heating temperature and heating time as described above, the residual stress in the resin composition layer can be removed and the adhesion surface can be smoothed. Heat aging may be performed after the step (c) described later.
[0023] Step (c): Etching step In step (c), etching is performed to remove or thin the encapsulation layer on the optical semiconductor element. By removing the encapsulation layer, the brightness of the optical semiconductor element is improved and visibility during light emission is ensured. The thickness of the encapsulation layer after etching is preferably approximately the same as the thickness of the optical semiconductor element as shown in FIG. 2(c-1), or less than the thickness of the optical semiconductor element as shown in FIG. 2(c-2). It is not necessary to completely remove the encapsulation layer from the optical semiconductor element, as long as it is substantially removed, and some thin film may remain. If sufficient brightness can be ensured, step (c) may be omitted. The etching method is not particularly limited, and preferred examples include wet etching methods such as chemical polishing using chemicals, physical polishing using an abrasive, laser etching, plasma etching using argon plasma or oxygen plasma, and dry etching methods such as ion beam etching. From the viewpoint of reducing the surface unevenness, it is preferable to use plasma etching or a combination of wet etching and dry etching. The plasma etching conditions may be, for example, dry etching in an anisotropic plasma device using a mixed gas of CF4 / O2 / N2 at an output of 1500-3000 W for 180-600 seconds, where the CF4 gas supply rate is, for example, 50-100 sccm, the O2 gas supply rate is, for example, 500-1000 sccm, and the N2 gas supply rate is, for example, 50-100 sccm.
[0024] As described above, through steps (a) to (c), the sealing layer can be formed from the resin composition layer. Next, the components of the encapsulating sheet of the present disclosure will be described in detail while citing preferred examples.
[0025] [Resin composition layer] The resin composition layer contains a resin (A) and metal oxide particles (B), and preferably further contains a crosslinking agent and / or a polymerization initiator, and may contain other components. The resin (A) is a substance that acts as a binder to bond and fix objects together, specifically to a substrate having an optical semiconductor element or to a substrate having an optical semiconductor element.
[0026] The refractive index of the resin composition layer is 1.45 to 1.65, preferably 1.47 to 1.60, and more preferably 1.49 to 1.55. By setting the refractive index within the above range, seamlessness and visibility are improved. The refractive index can be adjusted by the type and composition of the resin (A) and the type, dispersion state and content of the metal oxide particles (B). The refractive index can be increased by increasing the content of the aromatic ring structure in the resin (A) and the content of the metal oxide particles (B), and when a lower refractive index is desired, the opposite adjustment can be made.
[0027] The peak top strength (tan δ peak strength) of the loss tangent (tan δ) in the range of -50 to 80°C obtained by dynamic viscoelasticity measurement of the resin composition layer of the present disclosure is the value of the loss tangent (tan δ) when the tan δ curve is at its maximum, and when there are two or more peaks, it refers to the top strength of the peak on the lowest temperature side. The tan δ peak strength is preferably 0.6 to 2.2, more preferably 0.8 to 2.0, and even more preferably 0.9 to 1.8. By setting the tan δ peak strength within the above range, the resin composition layer is able to absorb pressure applied thereto in the pressing step well, and is able to conform to the optical semiconductor element while forming a uniform encapsulation layer, improving embeddability and adhesion. The tan δ peak intensity of the present disclosure can be adjusted by the type and composition of the resin (A), the type, dispersion state and content of the metal oxide particles (B), and the type and content of the monomer and / or oligomer. When the resin (A) contains a (meth)acrylic resin (a), the tan δ peak intensity can be made higher than when the resin (A) contains a urethane resin (b), but this is not always the case depending on the resin composition. When the resin (A) contains a (meth)acrylic resin (a), the tan δ peak intensity can be lowered by increasing the content of methacrylic acid alkyl ester such as methyl methacrylate, and when it is desired to increase the tan δ peak intensity, the opposite can be done. When the metal oxide particles (B) contain ZrO2, the tan δ peak intensity can be lower than when they contain TiO2, but this is not always the case depending on the dispersion state of the particles. When the metal oxide particles (B) contain ZrO2, the tan δ peak intensity can be lowered by increasing the content of ZrO2, and if it is desired to increase the tan δ peak intensity, the opposite can be adjusted. When the resin composition layer contains a monomer and / or oligomer, the tan δ peak intensity can be lowered by increasing the content of the low-viscosity monomer and / or oligomer, and the opposite can be done to increase the tan δ peak intensity. A specific example of a low-viscosity monomer is 1,6-hexanediol diacrylate, and a specific example of a low-viscosity oligomer is an oligomer having a weight-average molecular weight of 1,300 or less.
[0028] Furthermore, the loss tangent (tan δ40) at 40°C obtained by dynamic viscoelasticity measurement of the resin composition layer of the present disclosure is preferably 0.6 to 2.0, more preferably 0.8 to 1.9, and even more preferably 1.0 to 1.8. By setting tan δ40 within the above range, the pressure applied to the resin composition layer in the pressing step is appropriately diffused, improving embeddability and adhesion. In order to control the diffusivity of the pressure applied to the resin composition layer in the preferred temperature range of 20 to 200°C for the pressing process, the loss tangent at 40°C (tan δ40) can be adjusted to the above range, thereby achieving an even balance between the loss tangent at 20 to 40°C and the loss tangent at 40 to 200°C. The above-mentioned loss tangent (tan δ) is the ratio of loss modulus / storage modulus obtained by dynamic viscoelasticity measurement in a tensile mode at a frequency of 10 Hz and at -50 to 150°C. Tan δ40 can be adjusted by the type and composition of the resin (A) and the type and dispersion state of the metal oxide particles (B). Specifically, the same adjustment methods as for the tan δ peak intensity can be used.
[0029] The dynamic viscoelasticity and loss tangent (tan δ) in the present disclosure were measured by the method described in the Examples described later. In addition, when the resin composition layer contains any one of a photopolymerization initiator, a crosslinking agent, and a polymerization initiator, the crosslinking / polymerization reaction at the time of measurement is incomplete. In addition, the above measurement is preferably performed on a sheet having a thickness of 50 μm or more. When measuring a sheet having a thickness less than this, two sets of sealing sheets without release liners are prepared, the resin composition layers are bonded together with a laminator to prepare a laminate of protective film / resin composition layer / protective film, and the protective film on one side of the aforementioned laminate is peeled off, and the resin composition layers of the sealing sheets are repeatedly bonded together to obtain a thickness of 50 μm or more, after which the dynamic viscoelasticity may be measured.
[0030] From the viewpoint of embeddability and adhesion, the thickness Ta of the resin composition layer is preferably 1 to 100 μm, more preferably 5 to 50 μm, and even more preferably 5 to 30 μm. By setting the thickness Ta of the resin composition layer within the above range, the pressure is appropriately diffused in the resin composition layer in the pressing process and sufficiently smoothed, thereby improving the embeddability and adhesion. The resin composition layer may be in the form of a single layer or a laminate of two or more layers. The thickness Ta in the present disclosure was measured by the method described in the examples below.
[0031] Resin composition layer CIEL * a * b * Saturation in color space C * is preferably 0 to 10, more preferably 0 to 5, and further preferably 0 to 3.
[0032] Saturation C *is an index of the vividness of a color, and chromaticity a * and b * This is the value calculated using the following formula 1. C * =(a *2 +b *2 ) 0.5 (Formula 1)
[0033] In formula 1, C * is the saturation, and a * and b * are the chromaticity a * and b * All values were measured in accordance with JIS Z 8781-4. Saturation C * By setting the range above, the influence of the color tone of the coating film on the color tone of the optical semiconductor is suppressed, and seamlessness and visibility are improved. Saturation C in this disclosure * was measured by the method described in the Examples below. Saturation C in this disclosure * can be adjusted by the type of resin (A), the type and content of metal oxide particles (B), and the type and content of monomers and / or oligomers. When the resin (A) contains the (meth)acrylic resin (a), the chroma C can be increased by increasing the content of the functional group-containing monomer constituting the (meth)acrylic resin (a). * can be adjusted to be higher, and vice versa if desired to lower it. When the content of metal oxide particles (B) is increased, the chroma C * can be increased, and the saturation C * If it is desired to lower it, the opposite adjustment should be made. When the resin composition layer contains a monomer and / or an oligomer, the chroma C can be increased by increasing the number of functional groups in the monomer or by increasing the content of the functional group-containing monomer constituting the oligomer. * can be adjusted to be higher, and vice versa if desired to lower it.
[0034] The haze of the resin composition layer is preferably 12% or less, more preferably 8% or less, and even more preferably 5% or less. The haze in the present disclosure was measured by the method in the examples described below. The total light transmittance of the resin composition layer is preferably 80% or more, more preferably 85% or more, and even more preferably 90% or more. The total light transmittance of the resin composition layer was measured by the method described in the examples below. By setting the haze and total light transmittance of the resin composition layer within the above ranges, Less clutter and better seamlessness and visibility. The haze and total light transmittance of the resin composition layer in the present disclosure can be adjusted by the type of resin (A), the type, dispersion state and content of metal oxide particles (B), and the type and content of monomers and / or oligomers. When the resin (A) contains a (meth)acrylic resin (a) or when the metal oxide particles (B) contain ZrO2, the haze and the total light transmittance can be reduced.
[0035] [Method of forming resin composition layer] The method for forming the resin composition layer is not particularly limited, but a suitable example is a method for forming a resin composition layer by coating a resin composition in which an arbitrary solvent is added to the components constituting the resin composition layer. The solvent is added for the purpose of adjusting the viscosity level to a level suitable for coating. For coating, known coating machines and techniques such as a comma coater, a die coater, a roll coater, a lip coater, a reverse coater, a gravure coater, a bar coater, a curtain coater, dip coating, spin coating, silk screen, casting, etc. The solvent contained in the resin composition can be removed by a drying process after coating. In a preferred embodiment, the resin composition is applied to a support such as a protective film or a release liner, and then the coating film is heated and dried using a hot air oven, an infrared heater, or the like to form a resin composition layer on one side of the support. Furthermore, in order to increase the crosslink density of the resin composition layer, it is preferable to perform an aging treatment such as leaving it to stand under specific temperature conditions, or to irradiate it with UV or the like. After coating, the resin composition may be transferred to another support such as a protective film, a release liner, or a substrate using a laminator.
[0036] [Resin composition] The resin composition can be obtained by mixing a solvent, a resin (A), and metal oxide particles (B) while stirring. The optional solvent is used for the purpose of adjusting the processing suitability such as viscosity when mixing the resin (A) and the metal oxide particles (B), so that a solvent compatible with the resin (A), such as an ester type, an ether ester type, an ether type, an alcohol type, or an aromatic type, can be appropriately used. Specifically, acetone, 2-butanone, ethyl acetate, cyclohexanone, toluene, xylene, isopropyl alcohol, and N-methyl-2-pyrrolidone are suitable examples. For stirring, a known stirring device can be used, and a disperser, a mixer, a shaker, a homogenizer, or the like is preferable.
[0037] To obtain the resin composition, a two-stage or more manufacturing process may be adopted in which, first, a mixture is prepared by mixing the metal oxide particles (B) with the resin (A) and an arbitrary solvent, and, second, the resin (A), a crosslinking agent, a polymerization initiator, and other components are added as necessary.
[0038] Resin (A) The weight average molecular weight (Mw) of the resin (A) is preferably 10,000 to 1,000,000. From the viewpoint of light resistance and adhesion, it is more preferably 20,000 to 300,000, and even more preferably 30,000 to 150,000. By setting the weight average molecular weight (Mw) within the above range, entanglement of molecular chains is easily untangled in the heat aging process, improving adhesion. The ratio (Mw / Mn) of the number average molecular weight (Mn) to the weight average molecular weight (Mw), which indicates the degree of dispersion of the resin (A), is preferably 1 to 5, more preferably 2 to 4.5, and even more preferably 2.5 to 4. By setting Mw / Mn within the above range, the flow rate when the resin is heated is made uniform within the resin, making it easier to control the fluidity of the resin and improving embeddability. In addition, the speed at which the resin wets the adherend is also made uniform, improving adhesion. The weight average molecular weight (Mw) and number average molecular weight (Mn) are values measured in terms of polystyrene by gel permeation chromatography (GPC). The weight average molecular weight (Mw) and number average molecular weight (Mn) in the present disclosure are measured by the method described in the Examples below. It was determined.
[0039] The glass transition temperature (Tg) of the resin (A) is −30° C. to 60° C. From the viewpoint of embeddability and adhesion, −20° C. to 50° C. is more preferable, −15° C. to 40° C. is even more preferable, −10° C. to 30° C. is even more preferable, and 0° C. to 20° C. is most preferable. By setting the glass transition temperature (Tg) to −30° C. or higher, the fluidity and wettability of the resin (A) in the pressing step can be made favorable, and the embeddability and adhesion can be improved. By setting the glass transition temperature (Tg) to 60° C. or less, when pressure is applied to the resin composition layer in the pressing process, the molecular motion of the resin (A) contained in the resin composition layer becomes active, and the entanglement of molecular chains becomes easy to loosen. When the entanglement of molecular chains is loosened, it becomes possible for the resin (A) to deform so as to conform to an uneven adherend such as a substrate or an optical semiconductor element, and the gap between the optical semiconductor element and the resin composition layer can be reduced, leading to improved embeddability.
[0040] The glass transition temperature (Tg) of the resin (A) in this application refers to the glass transition temperature (Tg) before thermal crosslinking and before photocrosslinking when the resin (A) undergoes a crosslinking reaction due to heat or light. The glass transition temperature (Tg) of the resin (A) in this disclosure is measured by the method described in the examples below.
[0041] The resin (A) may be used alone or in combination of two or more. The content of the resin (A) is preferably 10 to 98 mass%, more preferably 40 to 95 mass%, and even more preferably 60 to 90 mass%, based on the total amount (100 mass%) of the resin composition layer. When two or more types of resin (A) are contained, the content of each of the resins (A) is preferably 5 mass% or more, and the total content is preferably within the above-mentioned range. By setting the content of the resin (A) within the above range, compatibility with the metal oxide particles (B) is improved, and visibility is improved.
[0042] Suitable examples of the resin (A) include (meth)acrylic resin (a), urethane resin (b) such as polyurethane resin or polyurethane urea resin, maleic acid resin, styrene-maleic acid copolymer, polystyrene resin, polybutadiene resin, polyester resin, condensation type polyester resin, addition type polyester resin, melamine resin, epoxy resin, polycarbonate resin, oxetane resin, phenoxy resin, polyimide resin, polyamideimide resin, alkyd resin, amino resin, polyamide resin, polylactic acid resin, oxazoline resin, benzoxazine resin, silicone resin, fluororesin, butyral resin, chlorinated polyethylene, chlorinated polypropylene, polyvinyl chloride, vinyl chloride-vinyl acetate copolymer, polyvinyl acetate, vinyl resin, rubber resin, cyclized rubber resin, cellulose, polyethylene (HDPE, LDPE), etc. From the viewpoint of embeddability, it is preferable to contain at least one of (meth)acrylic resin (a) and urethane resin (b). Furthermore, from the viewpoint of adhesion, it is more preferable to contain (meth)acrylic resin (a).
[0043] The resin (A) preferably has a plurality of functional groups that can be utilized in a crosslinking reaction by heat or light. The functional groups may be appropriately selected depending on the combination with the crosslinking agent, the thermal polymerization initiator, and the photopolymerization initiator described later, and may be self-crosslinkable functional groups. Examples of the functional group include a hydroxyl group, a carboxyl group, an amino group, an epoxy group, an oxetanyl group, an oxazoline group, an oxazine group, an aziridine group, a thiol group, an isocyanate group, a blocked isocyanate group, a silanol group, a vinyl group, and an acryloyl group. From the viewpoint of dispersibility of the metal oxide particles (B), a carboxy group, a hydroxyl group, or an epoxy group is preferred. When the resin (A) has a carboxy group, the acid value of the resin (A) is preferably 1 to 45 mgKOH / g, more preferably 3 to 30 mgKOH / g, and further preferably 5 to 20 mgKOH / g. By setting the acid value of the resin (A) within the above range, the crosslinking density with the crosslinking agent is optimized, and the adhesion is improved. The acid value in this disclosure was measured by the method described in the Examples below.
[0044] When the crosslinking reaction is caused by light, the resin (A) preferably has one or more unsaturated bonds in one molecule, and also preferably contains a photopolymerization initiator. Examples of the photopolymerization initiator include triazine-based photopolymerization initiators, borate-based photopolymerization initiators, carbazole-based photopolymerization initiators, acetophenone-based photopolymerization initiators, and oxime ester-based photopolymerization initiators. The acetophenone-based photopolymerization initiators and oxime ester-based photopolymerization initiators are preferred because they are less likely to yellow during the heat aging process. From the viewpoint of preventing yellowing, the content of the photopolymerization initiator is preferably 0.5 to 10 mass %, and more preferably 0.5 to 5 mass %, based on the total amount (100 mass %) of the resin composition layer.
[0045] When the crosslinking reaction is caused by heat, preferred embodiments include a first embodiment in which a crosslinking agent is combined with the composition, and a second embodiment in which a thermal polymerization initiator is combined with the composition.
[0046] [(Meth)acrylic resin (a)] In the present disclosure, the (meth)acrylic resin (a) is an acrylic copolymer (polymer) obtained by copolymerizing a (meth)acrylic acid ester monomer, and is a polymer having structural units based on 25 to 20,000 monomers, and the weight average molecular weight of the (meth)acrylic resin (a) is 10,000 to 1,000,000. A suitable example of the (meth)acrylic acid ester monomer is a (meth)acrylic acid alkyl ester monomer. When a crosslinked structure is formed, a (meth)acrylic copolymer obtained by copolymerizing a functional group-containing monomer and a (meth)acrylic acid ester monomer is preferred.
[0047] The (meth)acrylic acid alkyl ester monomer is a compound in which an alkyl group or a cycloalkyl group is introduced by esterifying (meth)acrylic acid, and the alkyl group or the cycloalkyl group may be any of a linear, branched, or cyclic saturated aliphatic hydrocarbon group. The saturated aliphatic hydrocarbon group is preferably a saturated aliphatic hydrocarbon group having 1 to 20 carbon atoms, and more preferably a saturated aliphatic hydrocarbon group having 1 to 12 carbon atoms. Specific examples include methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, isopropyl (meth)acrylate, n-butyl (meth)acrylate, isobutyl (meth)acrylate, s-butyl (meth)acrylate, t-butyl (meth)acrylate, pentyl (meth)acrylate, hexyl (meth)acrylate, heptyl (meth)acrylate, octyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, isooctyl (meth)acrylate, nonyl (meth)acrylate, isononyl (meth)acrylate, and (meth)acrylic acid. Examples of the acrylates include decyl, isodecyl (meth)acrylate, undecyl (meth)acrylate, dodecyl (meth)acrylate, tridecyl (meth)acrylate, tetradecyl (meth)acrylate, pentadecyl (meth)acrylate, hexadecyl (meth)acrylate, heptadecyl (meth)acrylate, octadecyl (meth)acrylate, nonadecyl (meth)acrylate, eicosyl (meth)acrylate, lauryl (meth)acrylate, cyclohexyl (meth)acrylate, 4-n-butylcyclohexyl (meth)acrylate, and isobornyl (meth)acrylate. Among these, from the viewpoint of dispersibility of the metal oxide particles (B), it is particularly preferable to use methyl (meth)acrylate, n-butyl (meth)acrylate, hexyl (meth)acrylate, cyclohexyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, and lauryl (meth)acrylate, and it is most preferable to use methyl (meth)acrylate and n-butyl (meth)acrylate.
[0048] From the viewpoint of adhesion, the structural unit derived from a (meth)acrylic acid alkyl ester monomer is preferably 1 to 100% by mass relative to 100% by mass of the (meth)acrylic resin (a). The content is preferably 20 to 99.9% by mass, more preferably 80 to 99.7% by mass.
[0049] The (meth)acrylic resin (a) preferably has a structural unit derived from a functional group-containing monomer and / or an unsaturated bond. Examples of functional group-containing monomers include carboxyl group-containing monomers, hydroxyl group-containing monomers, epoxy group-containing monomers, and amino group-containing monomers. By including a functional group-containing monomer, the cohesive force of the resin (A) is improved, and a tough resin composition layer is obtained. In particular, it is preferable to include a carboxyl group-containing monomer, a hydroxyl group-containing monomer, and an epoxy group-containing monomer.
[0050] Examples of the carboxyl group-containing monomer include (meth)acrylic acid, β-carboxyethyl (meth)acrylate, p-carboxybenzyl (meth)acrylate, carboxypentyl (meth)acrylate, itaconic acid, maleic acid, fumaric acid, crotonic acid, citraconic acid, and isocrotonic acid. Among these, (meth)acrylic acid is preferred from the viewpoint of adhesion.
[0051] Examples of the hydroxyl group-containing monomer include 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, 6-hydroxyhexyl (meth)acrylate, 8-hydroxyoctyl (meth)acrylate, 10-hydroxydecyl (meth)acrylate, 12-hydroxylauryl (meth)acrylate, and (4-hydroxymethylcyclohexyl)methyl (meth)acrylate. Among these, from the viewpoint of adhesion, 4-hydroxybutyl (meth)acrylate, 2-hydroxyethyl (meth)acrylate, and 4-hydroxybutyl (meth)acrylate are more preferred.
[0052] Examples of the epoxy group-containing monomer include glycidyl (meth)acrylate, methyl glycidyl (meth)acrylate, 3,4-epoxycyclohexylmethyl (meth)acrylate, and 6-methyl-3,4-epoxycyclohexylmethyl (meth)acrylate. Among these, it is preferable to include glycidyl (meth)acrylate from the viewpoint of adhesion.
[0053] Examples of the amino group-containing monomer include monoalkylamino (meth)acrylates such as monomethylaminoethyl (meth)acrylate, monoethylaminoethyl (meth)acrylate, monomethylaminopropyl (meth)acrylate, and monoethylaminopropyl (meth)acrylate.
[0054] The total amount of structural units derived from functional group-containing monomers is preferably 0.1 to 20% by mass relative to 100% by mass of the (meth)acrylic resin (a). By setting the amount within this range, the cohesive strength can be adjusted by reaction with the crosslinking agent. The amount of the structural unit derived from the carboxyl group-containing monomer is preferably 0.1 to 10% by mass relative to 100% by mass of the (meth)acrylic resin (a). When the amount is within the above range, adhesion can be improved. The amount of the structural unit derived from the hydroxyl group-containing monomer is preferably 0.1 to 10% by mass relative to 100% by mass of the (meth)acrylic resin (a). When the amount is within the above range, adhesion can be improved. The epoxy group-containing monomer-derived structural unit is preferably 0.1 to 15% by mass relative to 100% by mass of the (meth)acrylic resin (a). When it is in this range, adhesion can be improved.
[0055] A more preferred example of the functional group-containing monomer constituting the (meth)acrylic resin (a) is one in which a carboxyl group-containing monomer and a hydroxyl group-containing monomer are not simultaneously contained, which can adjust the cohesive force of the (meth)acrylic resin (a) and increase the adhesion.
[0056] The (meth)acrylic resin (a) may contain structural units derived from other monomers copolymerizable with (meth)acrylic acid alkyl esters and functional group-containing monomers. Examples of such monomers include monomers having an alkyleneoxy group and other vinyl monomers. Examples of such monomers include methoxyethyl acrylate, methoxydiethylene glycol acrylate, vinyl acetate, vinyl crotonate, styrene, acrylonitrile, and acrylamide. The structural units derived from the other monomers are preferably 0.1 to 20% by mass in 100% by mass of the (meth)acrylic copolymer.
[0057] The (meth)acrylic resin (a) is obtained by polymerizing an acrylic monomer mixture. During polymerization, a polymerization initiator can be used as necessary. The content of the polymerization initiator is, for example, 0.01 to 10% by mass relative to 100% by mass of the monomer mixture. The polymerization method is not limited. For example, polymerization can be performed by solution polymerization, bulk polymerization, emulsion polymerization, or suspension polymerization, and solution polymerization is most preferable because of ease of polymerization control. Examples of the solvent used in solution polymerization include acetone, methyl acetate, ethyl acetate, toluene, xylene, anisole, methyl ethyl ketone, and cyclohexanone. The polymerization temperature can be, for example, 60 to 120°C, and the polymerization time can be about 2 to 12 hours.
[0058] The polymerization initiator is preferably a radical polymerization initiator. As the radical polymerization initiator, peroxides and azo compounds are suitable. Any of the thermal radical polymerization initiators described below can be used, and specifically, 2,2'-azobisisobutyronitrile (abbreviation: AIBN) is preferred.
[0059] [Urethane resin (b)] In the present disclosure, the urethane resin (b) is a general term for a compound containing two or more urethane bonds in one molecule. The urethane resin can be obtained by reacting a polyisocyanate with a polyol. The polyisocyanate may have two or more isocyanate groups in one molecule, and from the viewpoint of dispersibility of the metal oxide particles (B), diisocyanate or triisocyanate is preferable, and diisocyanate is more preferable. The diisocyanate may be appropriately selected from known aliphatic diisocyanates such as hexamethylene diisocyanate and known aromatic diisocyanates such as benzene-1,3-diisocyanate. In addition, an isocyanate-terminated prepolymer obtained by reacting a polyol with an excess of polyisocyanate may be used as an intermediate of the urethane resin. The polyol may have two or more hydroxyl groups in one molecule, and from the viewpoint of dispersibility of the metal oxide particles (B), a diol or triol is preferable, and a diol is more preferable. The diol may be appropriately selected from known aliphatic diols such as ethylene glycol and known aromatic diols such as benzene diol. Prepolymers such as polyether polyols, polyester polyols, and polycarbonate polyols may also be used.
[0060] The urethane resin (b) may be a polyurethane urea resin further having a urea bond. The polyurethane urea resin can be synthesized, for example, by reacting a urethane resin having an isocyanate group at its terminal with a polyamine. Polyamines are sufficient as long as they have two or more amino groups in one molecule. From the viewpoint of dispersibility of the molecule (B), diamines or triamines are preferred, and diamines are more preferred. The diamines can be appropriately selected from known aliphatic diamines such as ethylenediamine and known aromatic diamines such as phenylenediamine.
[0061] [Metal oxide particles (B)] In the present embodiment, the metal oxide particles (B) have the function of improving the fluidity of the resin (A) and improving the embedding property between optical semiconductor elements, and also have the function of adjusting the refractive index. Examples of metals constituting the metal oxide particles (B) include Ti, Al, Zr, In, Zn, Sn, La, Y, Ce, Mg, Hf, Ta, Ba, Ca, Si, etc., and from the viewpoint of improving embeddability and seamlessness, Ti, Al, and Zr are preferred, and Zr is more preferred. The metal oxide particles (B) may be used individually or in combination of two or more kinds.
[0062] Examples of the Ti-containing metal oxide particles (B) include titanium monoxide (TiO), titanium dioxide (TiO2), titanium trioxide (TiO3), barium titanate (BaTiO3), and perovskite (CaTiO3). Examples of the Al-containing metal oxide particles (B) include aluminum oxide (Al2O3) and spinel (MgAl2O4). An example of the Zr-containing metal oxide particles (B) is zirconium oxide (ZrO2). Among these, aluminum oxide (Al2O3), titanium dioxide (TiO2), and zirconium oxide (ZrO2) are preferable from the viewpoint of embedding properties, and zirconium oxide (ZrO2) is most preferable.
[0063] Other metal oxide particles (B) may include indium oxide (In2O3), zinc oxide (ZnO), tin oxide (SnO2), lanthanum oxide (La2O3), yttrium oxide (Y2O3), cerium oxide (CeO2), magnesium oxide (MgO), hafnium oxide (HfO2), tantalum pentoxide (Ta2O5), niobium pentoxide (Nb2O5), silicon dioxide (SiO2), indium tin oxide (ITO), antimony tin oxide (ATO), and the like.
[0064] The metal oxide particles (B) are preferably metal oxide particles whose surfaces are modified with a surface modifier, such as an organic acid, a silane coupling agent, a surfactant, a titanium coupling agent, or a metal impurity, and preferably contain an organic acid.
[0065] From the viewpoint of dispersibility, the metal oxide particles (B) should have a specific surface area of 10 to 400 m by the BET method. 2 / g, and 10 to 150m 2 / g is more preferable, and 20 to 84m 2 The specific surface area by the BET method can be measured in accordance with JIS Z 8830.
[0066] The number-average primary particle diameter of the metal oxide particles (B) is 5 to 50 nm, preferably 5 to 30 nm, more preferably 7 to 25 nm, and most preferably 10 to 20 nm. By setting it within the above range, the flowability of the resin composition layer is improved, and the embedding property is improved. In addition, the viscosity of the resin composition is easily maintained at a level suitable for coating. Furthermore, the dispersibility in the resin is improved, and the refractive index adjusting function is easily exhibited. The number-average primary particle diameter of the metal oxide particles (B) can be determined by randomly selecting 20 particles that can be observed from images of the metal oxide particles (B) magnified approximately 50,000 to 1,000,000 times using a transmission electron microscope (TEM), a field emission transmission electron microscope (FE-TEM), a field emission scanning electron microscope (FE-SEM), or the like, measuring the length of the particles in the long axis direction, and calculating the arithmetic average.
[0067] The content of the metal oxide particles (B) is preferably 1 to 40 mass%, more preferably 3 to 35 mass%, and even more preferably 5 to 30 mass%, based on the total amount (100 mass%) of the resin composition layer. By setting the content within the above range, the flow of the resin composition becomes favorable, and the embeddability becomes at an excellent level. In addition, the dispersibility in the resin becomes favorable, and the visibility is improved.
[0068] It is preferable to disperse the metal oxide particles (B) in the resin (A) and use it as a metal oxide particle dispersion from the viewpoint of adjusting the loss tangent (tan δ) and embeddability of the resin composition layer. The dispersing machine used for mechanical disintegration in the dispersion process may be any commonly used dispersing machine, for example, a ball mill, a roll mill, a sand mill, a bead mill, and a nanomizer. Among them, a bead mill is preferably used. Examples of such machines include a super mill, a sand grinder, an agitator mill, a grain mill, a dyno mill, a pearl mill, and a cobol mill (all trade names).
[0069] In the present disclosure, from the viewpoint of storage stability of the resin composition layer, it is preferable to use a dispersant in the dispersion treatment of the metal oxide particles (B). In the present disclosure, the dispersant has a function of imparting repulsive force between particles so that the particles divided through the above-mentioned dispersion treatment do not aggregate again. As the dispersant, a conventionally known compound can be used, and examples thereof include cationic, anionic or nonionic surfactants, cationic, anionic or nonionic polymer dispersants, and pigment derivative dispersants.
[0070] Examples of the polymeric dispersant include polyurethane resins, polyester resins, polyamide resins, (meth)acrylic resins, polycarboxylic acids (salts), styrene copolymers, polyalkylene oxide derivatives, and phosphate resins. The acid value of the polymeric dispersant is preferably 5 to 450 mgKOH / g, more preferably 46 to 300 mgKOH / g, and even more preferably 50 to 200 mgKOH / g. If the polymeric dispersant has a moderate acid value, an excellent electrostatic repulsion effect can be obtained, and a dispersion having excellent storage stability can be obtained. The acid value in the present disclosure is measured by the method described in the examples below. The weight average molecular weight (Mw) of the polymer dispersant is preferably 1,000 to 50,000, more preferably 3,000 to 30,000. If the polymer dispersant has a suitable weight average molecular weight (Mw), the adsorption rate to the colorant is improved, and a dispersion having excellent stability can be obtained. The weight average molecular weight (Mw) in the present disclosure is measured by the method described in the examples below.
[0071] Pigment derivative dispersants are compounds having an acidic group, a basic group, a neutral group, etc. in the organic dye residue. Examples include compounds having an acidic substituent such as a sulfo group, a carboxyl group, or a phosphoric acid group, as well as amine salts thereof, compounds having a basic substituent such as a sulfonamide group, an amide group, or a tertiary amino group at the end, and compounds having a neutral substituent such as a phenyl group or a phthalimidoalkyl group. Examples of organic dyes include phthalocyanine pigments, diketopyrrolopyrrole pigments, anthraquinone pigments, quinacridone pigments, dioxazine pigments, perinone pigments, perylene pigments, thiazine indigo pigments, triazine pigments, benzimidazolone pigments, indole pigments such as benzoisoindole, isoindoline pigments, isoindolinone pigments, quinophthalone pigments, naphthol pigments, threne pigments, metal complex pigments, azo pigments such as azo, disazo, and polyazo, etc. These dispersants may be used either individually or in combination of two or more. By using these dispersants, it becomes possible to prevent the aggregation over time of the metal oxide particles (B) contained in the resin composition layer, and to prevent unevenness in the encapsulating sheet.
[0072] The content of the dispersant (the total content when two or more kinds are contained) is preferably 0.01 to 10 mass % based on the total amount (100 mass %) of the resin composition layer, and more preferably 0.1 to 5 mass %. By containing the dispersant in an amount of 0.01% by mass or more, the cohesion property of the resin composition layer over time becomes good, and by containing the dispersant in an amount of 10% by mass or less, the viscosity of the dispersion of the metal oxide particles (B) falls within a suitable range, and the coating suitability becomes good.
[0073] [First embodiment] In the first embodiment according to the present disclosure, the resin composition layer contains a resin (A) and a crosslinking agent. The first embodiment is characterized in that the resin composition layer is heated, whereby a crosslinked structure is formed by reacting a functional group of the resin (A) with the crosslinking agent. From the viewpoint of coating film strength, it is preferable to use the resin (A) having a weight average molecular weight (Mw) of 10,000 or more, and it is more preferable to use the (meth)acrylic resin (a).
[0074] [Crosslinking agent] In the first embodiment, the resin composition layer of the present disclosure preferably contains a crosslinking agent to promote the formation of a crosslinked structure. The crosslinking agent may be used alone or in combination of two or more. The crosslinking agent increases the cohesive force of the resin composition layer and improves adhesion by crosslinking with the reactive functional group of the resin (A) during heat pressing or heat aging in the pressing process. The crosslinking agent has a plurality of functional groups capable of reacting with the functional groups of the resin (A). Examples of the crosslinking agent include known compounds such as silane coupling agents, epoxy crosslinking agents, acid anhydride group-containing compounds, imidazole compounds, isocyanate compounds, aziridine compounds, and amine compounds. From the viewpoint of adjusting the loss tangent (tan δ) of the resin composition layer, silane coupling agents, epoxy crosslinking agents, aziridine compounds, imidazole compounds, and isocyanate compounds are preferred, and from the viewpoint of adhesion, epoxy crosslinking agents are more preferred.
[0075] A silane coupling agent is a compound in which a hydrolyzable group such as a methoxy group or an ethoxy group and a functional group such as an epoxy group are bonded to a silicon atom via an alkylene group. Examples of the silane coupling agent include alkoxysilane compounds having a (meth)acryloxy group, such as 3-(meth)acryloxypropyltrimethoxysilane, 3-(meth)acryloxypropyltriethoxysilane, 3-(meth)acryloxypropyltripropoxysilane, 3-(meth)acryloxypropyltributoxysilane, 3-(meth)acryloxypropylmethyldimethoxysilane, and 3-(meth)acryloxypropylmethyldiethoxysilane; Alkoxysilane compounds having a vinyl group, such as vinyltrimethoxysilane, vinyltriethoxysilane, vinyltriisopropoxysilane, vinyltributoxysilane, vinylmethyldimethoxysilane, and vinylmethyldiethoxysilane; alkoxysilane compounds having an amino group, such as 3-aminopropyltrimethoxysilane, 3-aminopropyltriethoxysilane, 3-aminopropyltripropoxysilane, 3-aminopropylmethyldimethoxysilane, 3-aminopropylmethyldiethoxysilane, N-(2-aminoethyl)-3-aminopropyltrimethoxysilane, N-(2-aminoethyl)-3-aminopropyltriethoxysilane, N-(2-aminoethyl)-3-aminopropylmethyldimethoxysilane, N-(2-aminoethyl)-3-aminopropylmethyldiethoxysilane, and N-phenyl-3-aminopropyltrimethoxysilane; alkoxysilane compounds having a mercapto group, such as 3-mercaptopropyltrimethoxysilane, 3-mercaptopropyltriethoxysilane, 3-mercaptopropyltripropoxysilane, 3-mercaptopropylmethyldimethoxysilane, and 3-mercaptopropylmethyldiethoxysilane; 3-Glycidoxypropyltrimethoxysilane, 3-Glycidoxypropyltriethoxysilane, 3-Glycidoxypropyltripropoxysilane, 3-Glycidoxypropyltributoxysilane, 3-Glycidoxypropylmethyldimethoxysilane, 3-Glycidoxypropylmethyldiethoxysilane, 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane Alkoxysilane compounds having an epoxy group, such as trimethoxysilane; tetraalkoxysilane compounds such as tetramethoxysilane, tetraethoxysilane, tetrapropoxysilane, and tetrabutoxysilane; Examples of the silane include 3-chloropropyltrimethoxysilane, n-hexyltrimethoxysilane, n-hexyltriethoxysilane, n-decyltrimethoxysilane, n-decyltriethoxysilane, styryltrimethoxysilane, phenyltrimethoxysilane, diphenyldimethoxysilane, 3-triethoxysilyl-N-(1,3-dimethylbutylidene)propylamine, 1,3,5-tris(3-trimethoxysilylpropyl)isocyanurate, 3-isocyanatepropyltrimethoxysilane, 3-isocyanatepropyltriethoxysilane, hexamethyldisilazane, and silicone resins having alkoxysilyl groups in the molecule. From the viewpoint of adhesion, alkoxysilane compounds are preferred, and 3-glycidoxypropyltrimethoxysilane is more preferred.
[0076] The epoxy-based crosslinking agent is a compound having two or more epoxy groups in one molecule, other than the above-mentioned (meth)acrylic resin (a) having an epoxy group-containing monomer. Regarding the properties of the epoxy-based crosslinking agent, the use of a liquid form can lower the tan δ peak temperature of the resin composition layer and improve adhesion between the optical semiconductor element and the resin composition layer, whereas the use of a solid form can increase the tan δ peak temperature of the resin composition layer and control the stickiness of the resin composition layer to adjust seamlessness. Examples of the epoxy crosslinking agent include a glycidyl ether type epoxy crosslinking agent, a glycidyl amine type epoxy crosslinking agent, a glycidyl ester type epoxy crosslinking agent, a cyclic aliphatic (alicyclic) epoxy crosslinking agent, a bisphenol type epoxy crosslinking agent, a hydrogenated bisphenol type epoxy crosslinking agent, and the like. From the viewpoint of adhesion, the bisphenol type epoxy crosslinking agent and the hydrogenated bisphenol type epoxy crosslinking agent are preferred.
[0077] Examples of the glycidyl ether type epoxy crosslinking agent include cresol novolac type epoxy crosslinking agents, tris(glycidyloxyphenyl)methane, and tetrakis(glycidyloxyphenyl)ethane. Examples of the glycidylamine type epoxy crosslinking agent include tetraglycidyldiaminodiphenylmethane and tetraglycidylmetaxylylenediamine. Examples of the glycidyl ester type epoxy crosslinking agent include diglycidyl phthalate, diglycidyl hexahydrophthalate, and diglycidyl tetrahydrophthalate. Examples of cyclic aliphatic (alicyclic) epoxy crosslinking agents include epoxycyclohexylmethyl-epoxycyclohexanecarboxylate, bis(epoxycyclohexyl)adipate, and the like. Examples of bisphenol type epoxy crosslinking agents include bisphenol A type epoxy crosslinking agents, bisphenol F type epoxy crosslinking agents, bisphenol S type epoxy crosslinking agents, bisphenol AD type epoxy crosslinking agents, etc. In particular, bisphenol A type epoxy crosslinking agents are preferred from the viewpoint of adhesion. Examples of hydrogenated bisphenol type epoxy crosslinking agents include hydrogenated bisphenol A type epoxy crosslinking agents, hydrogenated bisphenol F type epoxy crosslinking agents, etc. In particular, hydrogenated bisphenol A type epoxy crosslinking agents are preferred from the viewpoint of adhesion.
[0078] Examples of the aziridine compound include trimethylolpropane-tri-β-aziridinyl propionate, tetramethylolmethane-tri-β-aziridinyl propionate, N,N'-diphenylmethane-4,4'-bis(1-aziridinecarboxamide), N,N'-hexamethylene-1,6-bis(1-aziridinecarboxamide), tris- Examples thereof include 2,4,6-(1-aziridinyl)-1,3,5-triazine and 4,4'-bis(ethyleneiminocarbonylamino)diphenylmethane.
[0079] The imidazole compounds are 2-methylimidazole, 2-phenyl-4-methylimidazole, 2,4-dimethylimidazole, 2-phenylimidazole, imidazole, 2-undecylimidazole, 1-benzyl-2-methylimidazole, 1-benzyl-2-phenylimidazole, 1-cyanoethyl-2-undecylimidazole, 1-cyanoethyl-2-ethyl-4-methylimidazole, 1-cyanoethyl-2-phenylimidazolium trimellitate, 2,4-diamino-6-[2'-methylimidazolyl-(1')]- Examples of imidazole compounds include ethyl-s-triazine, 2,4-diamino-6-[2'-undecylimidazolyl-(1')]-ethyl-s-triazine, 2-phenylimidazole isocyanuric acid adduct, 2-phenyl-4,5-dihydroxymethylimidazole, and 2-phenyl-4-methyl-5-hydroxymethylimidazole. Further examples include compounds with improved storage stability, such as a type insoluble in a solvent obtained by reacting an imidazole compound with an epoxy resin, or a type in which an imidazole compound is encapsulated in a microcapsule.
[0080] The isocyanate compound is an isocyanate having two or more isocyanate groups. The isocyanate compound is preferably, for example, an isocyanate monomer such as an aromatic polyisocyanate, an aliphatic polyisocyanate, an araliphatic polyisocyanate, or an alicyclic polyisocyanate, as well as a biuret, a nurate, or an adduct thereof.
[0081] Examples of aromatic polyisocyanates include 1,3-phenylene diisocyanate, 4,4'-diphenyl diisocyanate, 1,4-phenylene diisocyanate, 4,4'-diphenylmethane diisocyanate, 2,4-tolylene diisocyanate, 2,6-tolylene diisocyanate, 4,4'-toluidine diisocyanate, 2,4,6-triisocyanate toluene, 1,3,5-triisocyanate benzene, dianisidine diisocyanate, 4,4'-diphenyl ether diisocyanate, and 4,4',4"-triphenylmethane triisocyanate. 2,4-tolylene diisocyanate is preferred from the viewpoint of adhesion. Examples of aliphatic polyisocyanates include trimethylene diisocyanate, tetramethylene diisocyanate, hexamethylene diisocyanate (also known as HDI), pentamethylene diisocyanate, 1,2-propylene diisocyanate, 2,3-butylene diisocyanate, 1,3-butylene diisocyanate, dodecamethylene diisocyanate, and 2,4,4-trimethylhexamethylene diisocyanate. Examples of the aromatic aliphatic polyisocyanate include ω,ω'-diisocyanate-1,3-dimethylbenzene, ω,ω'-diisocyanate-1,4-dimethylbenzene, ω,ω'-diisocyanate-1,4-diethylbenzene, 1,4-tetramethylxylylene diisocyanate, and 1,3-tetramethylxylylene diisocyanate. Examples of alicyclic polyisocyanates include 3-isocyanatemethyl-3,5,5-trimethylcyclohexyl isocyanate (also known as IPDI, isophorone diisocyanate), 1,3-cyclopentane diisocyanate, 1,3-cyclohexane diisocyanate, 1,4-cyclohexane diisocyanate, methyl-2,4-cyclohexane diisocyanate, methyl-2,6-cyclohexane diisocyanate, 4,4'-methylenebis(cyclohexyl isocyanate), and 1,4-bis(isocyanatemethyl)cyclohexane.
[0082] The biuret form is a self-condensation product having a biuret bond formed by self-condensation of an isocyanate monomer, for example, a biuret form of hexamethylene diisocyanate. The nurate form is a trimer of an isocyanate monomer, such as a trimer of hexamethylene diisocyanate, a trimer of isophorone diisocyanate, or a trimer of tolylene diisocyanate. The adduct is a bifunctional or higher isocyanate compound obtained by reacting an isocyanate monomer with a bifunctional or higher low-molecular active hydrogen-containing compound. Examples of the adduct include a compound obtained by reacting trimethylolpropane with hexamethylene diisocyanate, a compound obtained by reacting trimethylolpropane with tolylene diisocyanate, a compound obtained by reacting trimethylolpropane with xylylene diisocyanate, a compound obtained by reacting trimethylolpropane with isophorone diisocyanate, and a compound obtained by reacting 1,6-hexanediol with hexamethylene diisocyanate.
[0083] The isocyanate compound is preferably a trifunctional isocyanate compound from the viewpoint of forming a sufficient crosslinked structure. The isocyanate compound is more preferably an adduct which is a reaction product between an isocyanate monomer and a trifunctional low molecular weight active hydrogen-containing compound, and a nurate. The isocyanate compound is preferably a trimethylolpropane adduct of hexamethylene diisocyanate, a nurate of hexamethylene diisocyanate, a trimethylolpropane adduct of tolylene diisocyanate, a nurate of tolylene diisocyanate, a trimethylolpropane adduct of isophorone diisocyanate, or a nurate of isophorone diisocyanate, and more preferably a trimethylolpropane adduct of hexamethylene diisocyanate, a trimethylolpropane adduct of tolylene diisocyanate, or a trimethylolpropane adduct of isophorone diisocyanate.
[0084] In the first embodiment, from the viewpoint of coating film strength, it is preferable to contain two or more types of crosslinking agents. From the viewpoint of adjusting the loss tangent (tan δ) of the resin composition layer, specific preferred examples include two or more types selected from a silane coupling agent, an epoxy-based crosslinking agent, an aziridine compound, and an isocyanate compound.
[0085] The content of the crosslinking agent (total content when two or more kinds are used in combination) is preferably 0.01 to 30 mass %, more preferably 0.05 to 20 mass %, and even more preferably 0.1 to 10 mass %, based on the total amount (100 mass %) of the resin composition layer. By setting the content within the above range, embeddability and adhesion can be suitably adjusted.
[0086] [Crosslinking adjustment component] The resin composition layer of the first embodiment preferably contains a crosslinking adjusting component such as a crosslinking accelerator or a crosslinking retarder in order to adjust the crosslinking rate and the physical properties of the resin composition layer. The crosslinking accelerator is not particularly limited and can be appropriately selected. Specific examples of the crosslinking accelerator include, for example, a phosphorus-based crosslinking accelerator, an amine-based crosslinking accelerator, and a guanidine-based crosslinking accelerator. These may be used alone or in combination of two or more. From the viewpoint of coating suitability, the content of the crosslinking accelerator is preferably 0.01 to 10 mass %, and more preferably 0.1 to 5 mass %, based on the total amount (100 mass %) of the resin composition layer.
[0087] [Second embodiment] In the second embodiment of the present disclosure, the resin composition layer contains a resin (A) and a thermal polymerization initiator. Furthermore, the resin composition layer preferably contains a monomer and / or an oligomer. The second embodiment is characterized in that by heating the resin composition layer, radicals or ions (cations or anions) are generated from the thermal polymerization initiator, and a polymerization reaction occurs at an unsaturated bond site in any of the resin (A), the monomer, or the oligomer, resulting in a high molecular weight resin composition layer. When the resin composition layer contains a monomer or an oligomer, the resin (A), the monomer, and the oligomer may bond to each other. From the viewpoint of coating strength, it is preferable to use the resin (A) having a weight average molecular weight (Mw) of 10,000 or more, and it is more preferable to use the (meth)acrylic resin (a).
[0088] [Thermal polymerization initiator] In the present embodiment, a thermal cationic polymerization initiator or a thermal radical polymerization initiator can be used as the thermal polymerization initiator. From the viewpoint of storage stability of the resin composition layer, a thermal radical polymerization initiator is preferred. These initiators may be used alone or in combination of two or more. A thermal cationic polymerization initiator has a function of generating ions by heat. As the cationic component of the thermal cationic polymerization initiator, there are sulfonium cations, quaternary ammonium cations, iodonium cations, etc. As the anionic component, there are antimony hexafluoride anions, phosphorus hexafluoride anions, tetrakis(pentafluorophenyl)borate anions, trifluoromethanesulfonic acid, etc. The thermal radical polymerization initiator has a function of generating radicals by heat, and examples of the thermal radical polymerization initiator include an azo thermal polymerization initiator and an organic peroxide polymerization initiator.
[0089] Examples of organic peroxide polymerization initiators include diacetyl peroxide, di-t-butyl peroxide, di-t-hexyl peroxide, dicumyl peroxide, t-butylcumyl peroxide, α,α'-bis(t-butylperoxy-m-isopropyl)benzene, 2,5-dimethyl-2,5-bis(t-butylperoxy)hexyne-3, 2,5-dimethyl-2,5-bis(t-butylperoxy)hexane, 1,3-bis(t-butylperoxyisopropyl)hexane, (2-ethylhexanoyl)(t-butyl) Dialkyl peroxides such as peroxide; Dipropionyl peroxide, t-butyl peroxyacetate, t-butyl peroxybenzoate, 2,5-dimethyl-2,5-di(benzoylperoxy)hexane, bis(3,5,5-trimethylhexanoyl)peroxide, 1,1,3,3-tetramethylbutyl peroxyneodecanoate, α-cumyl peroxyneodecanoate, t-butyl peroxyneodecanoate, t-hexyl peroxyneodecanoate, t-butyl peroxyneoheptanoate, t-hexyl peroxypivalate, t-butyl peroxypivalate, 1,1,3,3-tetramethylbutyl peroxy-2-ethylhexanoate, t-amyl peroxy-2-ethylhexanoate, t-butyl peroxy-2-ethylhexanoate, Peroxyesters such as t-butylperoxyisobutyrate, di-t-butylperoxyhexahydroterephthalate, 1,1,3,3-tetramethylbutylperoxy-3,5,5-trimethylhexanate, t-amylperoxy-3,5,5-trimethylhexanoate, t-butylperoxy-3,5,5-trimethylhexanoate, dibutylperoxytrimethyladipate, 2,5-dimethyl-2,5-di-2-ethylhexanoylperoxyhexane, t-hexylperoxy-2-ethylhexanoate, t-hexylperoxyisopropyl monocarbonate, t-butylperoxylaurate, t-butylperoxyisopropyl monocarbonate, and t-butylperoxy-2-ethylhexyl monocarbonate; Ketone peroxides such as methyl ethyl ketone peroxide, methyl isobutyl ketone peroxide, acetylacetone peroxide, cyclohexanone peroxide, 3,3,5-trimethylcyclohexanone peroxide, methylcyclohexanone peroxide, t-butyl benzoate, and pivaloyl t-butyl peroxide; Peroxyketals such as 2,2-bis(t-butylperoxy)butane, 2,2-bis(4,4-di-t-butylperoxycyclohexyl)propane, 1,1-bis(t-butylperoxy)-3,3,5-trimethylcyclohexane, 1,1-bis(t-hexylperoxy)-3,3,5-trimethylcyclohexane, 1,1-bis(t-butylperoxy)cyclohexane, 1,1-bis(t-hexylperoxy)cyclohexane, and 4,4-bis(t-butylperoxy)butylpentanoate; Hydroperoxides such as t-butyl hydroperoxide, cumene hydroperoxide, diisopropylbenzene hydroperoxide, 2,5-dimethylcyclohexane-2,5-dihydroperoxide, 1,1,3,3-tetramethylbutyl hydroperoxide, and p-menthane hydroperoxide; Diacyl peroxides such as dibenzoyl peroxide, didecanoyl peroxide, dilauroyl peroxide, diisobutyryl peroxide, bis-3,5,5-trimethylhexanol peroxide, m-toluoylbenzoyl peroxide, succinic acid peroxide, and 2,4-dichlorobenzoyl peroxide; Examples of peroxydicarbonates include, but are not limited to, bis(t-butylcyclohexyl)peroxydicarbonate, diisopropyl peroxydicarbonate, di-n-propyl peroxydicarbonate, di(2-ethoxyethyl)peroxydicarbonate, t-butylperoxyisopropyl carbonate, di-2-ethylhexyl peroxydicarbonate, di-sec-butyl peroxycarbonate, di-3-methoxybutyl peroxydicarbonate, di-2-ethylhexyl peroxydicarbonate, t-amylperoxyisopropyl carbonate, t-butylperoxy-2-ethylhexyl carbonate, and 6-bis(t-butylperoxycarboxyloxy)hexane. From the viewpoint of storage stability, dialkyl peroxides are preferred, and di-t-butyl peroxide is more preferred.
[0090] Examples of the azo thermal polymerization initiator include 2,2'-azobisbutyronitrile such as 2,2'-azobisisobutyronitrile and 2,2'-azobis(2-methylbutyronitrile); 2,2'-azobisvaleronitrile such as 2,2'-azobis(4-methoxy-2,4-dimethylvaleronitrile), 2,2'-azobis(2,4-dimethylvaleronitrile), and 2,2'-azobis(2,4-dimethyl-4-methoxyvaleronitrile); 1,1'-azobis-1-alkanenitriles such as 1,1'-azobis(cyclohexane-1-carbonitrile) 2,2'-azobispropionitriles such as 2,2'-azobis(2-hydroxymethylpropionitrile) and 2,2'-azobis(2-hydroxymethylpropionitrile); 2,2'-azobispropionamides such as 2,2'-azobis(N-butyl-2-methylpropionamide) and 2,2'-azobis(N-cyclohexyl-2-methylpropionamide); Other examples include dimethyl 2,2'-azobis(2-methylpropionate), 2,2'-azobis[2-(2-imidazolin-2-yl)propane], and 1-[(1-cyano-1-methylethyl)azo]formamide. Examples of azo compounds having a carboxyl group or a hydroxyl group include, but are not limited to, 4,4'-azibis(4-cyanopentanoic acid), 4,4'-azobis(4-cyanovaleric acid), 2,2'-azobis(2-methyl-N-(2-hydroxyethyl)propionamide), and 2,2'-azobis(N-(carboxyethyl)-2-methylpropionamidine) tetrahydrate. From the viewpoint of storage stability, 2,2'-azobispropionamides are preferred, and 2,2'-azobis(N-butyl-2-methylpropionamide) is more preferred.
[0091] The 10-hour half-life temperature of the thermal radical polymerization initiator is preferably 60 to 200° C., more preferably 80 to 180° C., further preferably 100 to 150° C., and most preferably 105 to 130° C. By setting the temperature to 60° C. or higher, the storage stability of the resin composition layer can be improved, and by setting the temperature to 200° C. or lower, the heat aging step of the sealing layer can be shortened.
[0092] The 10-hour half-life temperature is the temperature at which the thermal polymerization initiator is thermally decomposed to half of its initial value after 10 hours. A thermal polymerization initiator solution is prepared by using the above method and sealed in a glass tube that has been purged with nitrogen. This is then immersed in a thermostatic chamber set at a specified temperature for 10 hours to cause thermal decomposition, and the amount of remaining thermal polymerization initiator is measured. This series of steps is carried out at several temperatures, and the half-life can be calculated from the straight line that is plotted.
[0093] The content of the thermal radical polymerization initiator (total content when two or more types are used in combination) is preferably 0.01 to 20 mass% based on the total amount (100 mass%) of the resin composition layer, more preferably 0.05 to 10 mass%, and even more preferably 0.1 to 5 mass%. By setting the content within the above range, the adhesion can be suitably adjusted.
[0094] [monomer] In the present embodiment, a monomer refers to a compound having a radical polymerizable group, which is the minimum structural unit for constituting an oligomer or a polymer. Examples of radical polymerizable groups include (meth)acryloyl groups, N-vinyl groups, vinyl ether groups, allyl groups, and unsaturated carboxylic acid groups. The monomer may be a monofunctional monomer or a polyfunctional monomer. In this specification, "monofunctional" refers to a compound having only one polymerizable group in one molecule, and "bifunctional" and "trifunctional" refer to compounds having two and three polymerizable groups in one molecule, respectively. In this specification, bifunctional or more functional groups are collectively referred to as "polyfunctional".
[0095] Specific examples of monomers include 2-methoxyethyl (meth)acrylate, methoxytriethylene glycol (meth)acrylate, dipropylene glycol (meth)acrylate, methoxydipropylene glycol (meth)acrylate, 2-ethoxyethyl (meth)acrylate, 2-(2-ethoxyethoxy)ethyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, 2-ethylhexyl EO-modified (meth)acrylate, 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, β-carboxyethyl (meth)acrylate, and phthalic acid monohydrogen. 4-t-butylcyclohexyl (meth)acrylate, tetrahydrofurfuryl acrylate, alkoxylated tetrahydrofurfuryl acrylate, caprolactone (meth)acrylate, isononyl (meth)acrylate, n-octyl (meth)acrylate, isooctyl (meth)acrylate, lauryl (meth)acrylate, stearyl (meth)acrylate, isoamyl (meth)acrylate, 2-phenoxyethyl (meth)acrylate, isodecyl (meth)acrylate, tridecyl (meth)acrylate, 3,3,5-trimethylcyclohexyl (meth)acrylate, cyclohexyl (meth)acrylate Acrylate, trimethylcyclohexyl (meth)acrylate, t-butylcyclohexyl (meth)acrylate, isobornyl (meth)acrylate, norbornyl (meth)acrylate, dicyclopentanyl (meth)acrylate, dicyclopentenyl (oxyethyl) (meth)acrylate, 1,4-Cyclohexanedimethanol (meth)acrylate, cyclic trimethylolpropane formal (meth)acrylate, benzyl (meth)acrylate, phenol EO modified (meth)acrylate, EO modified (2) nonylphenol acrylate, PO modified nonylphenol acrylate, phenoxyethyl (meth)acrylate, phenoxypolyethylene glycol (meth)acrylate, 2-hydroxy-3-phenoxypropyl (meth)acrylate, 2-methyl-2-ethyl-1,3-dioxy Monofunctional (meth)acrylate monomers having one (meth)acryloyl group in the molecule, such as xanthane-4-yl)methyl acrylate, hydroxyethyl acrylamide, dimethylaminopropyl acrylamide, N-acryloyloxyethyl hexahydrophthalimide, acryloylmorpholine, 3-((meth)acryloyloxy)propyl trimethoxysilane, 3-((meth)acryloyloxy)propyl triethoxysilane, and 2-(meth)acryloyloxyethyl isocyanate, Monofunctional vinyl monomers having one N-vinyl group in the molecule, such as N-vinylcarbazole, 1-vinylimidazole, N-vinyl-2-pyrrolidone, N-vinylcaprolactam, N-vinylformamide, N-vinyloxazolidinone, and N-vinylmethyloxazolidinone; 1,3-Butylene glycol di(meth)acrylate, 1,4-Butanediol di(meth)acrylate, 3-Methyl-1,5-Pentanediol di(meth)acrylate, 1,6-Hexanediol di(meth)acrylate, 1,9-Nonanediol di(meth)acrylate, 1,10-Decanediol di(meth)acrylate, 1,2-Dodecanediol di(meth)acrylate, Neopentyl glycol di(meth)acrylate, Polyethylene glycol (200) di(meth)acrylate , polyethylene glycol (300) di(meth)acrylate, polyethylene glycol (400) di(meth)acrylate, polyethylene glycol (600) di(meth)acrylate, hydroxypivalic acid neopentyl glycol di(meth)acrylate, dipropylene glycol di(meth)acrylate, tripropylene glycol di(meth)acrylate, EO modified (2) 1,6-hexanediol di(meth)acrylate, PO modified 1,6-hexanediol di(meth)acrylate , EO modified neopentyl glycol di(meth)acrylate, PO modified (2) neopentyl glycol di(meth)acrylate, (neopentyl glycol modified) trimethylolpropane di(meth)acrylate, trimethylol acid EO modified diacrylate, tricyclodecane di(meth)acrylate, dimethyloltricyclodecane di(meth)acrylate, bisphenol A di(meth)acrylate, EO modified (4) bisphenol A di(meth)acrylate, PO modified (4) bisphenol Bifunctional (meth)acrylate monomers having two (meth)acryloyl groups in the molecule, such as bisphenol A di(meth)acrylate, EO / PO modified bisphenol A di(meth)acrylate, bisphenol F di(meth)acrylate, EO modified bisphenol F di(meth)acrylate, PO modified bisphenol F di(meth)acrylate, cyclohexanedimethanol di(meth)acrylate, ethoxylated cyclohexanemethanol di(meth)acrylate, and dicyclopentanyl di(meth)acrylate, bifunctional (meth)acrylate monomers having one each of a (meth)acryloyl group and an allyl group in the molecule, such as 2-(allyloxymethyl)methyl acrylate and 2-(allyloxymethyl)ethyl acrylate; Trimethylolpropane tri(meth)acrylate, EO modified (3) Trimethylolpropane tri(meth)acrylate, EO modified (6) Trimethylolpropane tri(meth)acrylate, PO modified (3) Trimethylolpropane tri(meth)acrylate, ε-caprolactone modified tris-(2-acryloxyethyl)isocyanurate, ethoxylated isocyanuric acid tri(meth)acrylate, tris(2-hydroxyethyl)isocyanurate tri(meth)acrylate, pentaerythritol tri(meth)acrylate, tetramethylolmethane tri(meth)acrylate, dipentaerythritol tri(meth)acrylate, methylol trifunctional (meth)acrylate monomers having three (meth)acryloyl groups in the molecule, such as propane tri((meth)acryloyloxypropyl)ether, alkylene oxide-modified isocyanuric acid tri(meth)acrylate, dipentaerythritol propionate tri(meth)acrylate, tri((meth)acryloyloxyethyl)isocyanurate, hydroxypivalaldehyde-modified dimethylolpropane tri(meth)acrylate, sorbitol tri(meth)acrylate, propoxylated trimethylolpropane tri(meth)acrylate, EO-modified glycerin tri(meth)acrylate, and PO-modified glyceryl tri(meth)acrylate; Pentaerythritol tetra(meth)acrylate, EO modified (4) pentaerythritol tetra(meth)acrylate, ditrimethylolpropane tetra(meth)acrylate, sorbitol tetra(meth)acrylate, dipentaerythritol propionate tetra(meth)acrylate, tetramethylolmethane tetra(meth)acrylate, and other tetrafunctional (meth)acrylate monomers having four acryloyl groups in the molecule; Pentafunctional (meth)acrylate monomers having five (meth)acryloyl groups in the molecule, such as dipentaerythritol penta(meth)acrylate and sorbitol penta(meth)acrylate; Examples of the hexafunctional (meth)acrylate monomer having six (meth)acryloyl groups in the molecule include, but are not limited to, dipentaerythritol hexa(meth)acrylate, sorbitol hexa(meth)acrylate, alkylene oxide-modified hexa(meth)acrylate of phosphazene, and ε-caprolactone-modified dipentaerythritol hexa(meth)acrylate. In addition, the above "EO" refers to "ethylene oxide" and "PO" refers to "propylene oxide." The monomers may be used alone or in combination of two or more.
[0096] Among them, from the viewpoint of embedding property, the (meth)acrylate compound preferably contains a di- to hexa-functional (meth)acrylate monomer, and more preferably contains a di- or tri-functional (meth)acrylate monomer. Specifically, 1,6-hexanediol di(meth)acrylate, EO-modified (4) bisphenol A di(meth)acrylate, and EO-modified (3) trimethylolpropane tri(meth)acrylate are preferred.
[0097] The content of the monomer (total content when two or more kinds are used in combination) is preferably 0.01 to 30 mass% based on the total amount (100 mass%) of the resin composition layer, more preferably 0.05 to 20 mass%, and even more preferably 0.1 to 15 mass%. By setting the content within the above range, embeddability can be suitably adjusted.
[0098] [Oligomer] In the present embodiment, the oligomer refers to a polymer having constitutional units based on 2 to 100 monomers containing a radical polymerizable group, and has a weight average molecular weight of 400 to 9,999. The weight average molecular weight of the oligomer is more preferably 400 to 5,000, and further preferably 500 to 3,000. Examples of the polymerizable group of the oligomer include a (meth)acryloyl group, an N-vinyl group, a vinyl ether group, an allyl group, and an unsaturated carboxylic acid group, and the like, with a (meth)acryloyl group being preferred. The radical polymerizable oligomer may be monofunctional or polyfunctional. The number of polymerizable groups per molecule is preferably 1 to 6, and more preferably 2 to 4.
[0099] Specific examples of the oligomer include urethane acrylate oligomers such as aliphatic urethane acrylate oligomers and aromatic urethane acrylate oligomers, acrylic ester oligomers, polyester acrylate oligomers, epoxy acrylate oligomers, etc. The oligomers may be used alone or in combination of two or more kinds.
[0100] From the viewpoint of embedding properties, the (meth)acrylate compound of the present invention preferably contains an alkylene oxide-modified (meth)acrylate compound having two or more (meth)acryloyl groups in the molecule.
[0101] The content of the oligomer (total content when two or more kinds are used in combination) is preferably 0.01 to 30 mass% based on the total amount (100 mass%) of the resin composition layer, more preferably 0.05 to 20 mass%, and even more preferably 0.1 to 15 mass%. By setting the content within the above range, embeddability can be suitably adjusted.
[0102] [Other ingredients] The resin composition layer of the present disclosure may contain other components within the scope of the present disclosure. For example, colorants, dispersants, surface control additives, softeners, antistatic agents, lubricants, antiblocking agents, adhesion improvers, etc. may be added. From the viewpoint of controlling the film properties such as viscoelasticity of the resin composition layer, it is preferable to contain a colorant, a surface conditioning additive, and an adhesion improver.
[0103] Examples of the colorant include black pigments, black dyes, and pigments of red, green, blue, yellow, purple, cyan, magenta, etc., and a plurality of colorants can be mixed to obtain a desired color. Carbon black is preferable as the black pigment from the viewpoint of controlling the film properties. When the colorant is a pigment, the number average primary particle diameter is preferably 10 to 100 nm. By setting the colorant in the above range, the viscosity of the resin composition can be easily maintained at a level suitable for coating. The number average primary particle diameter of the pigment can be determined by the same method as that of the metal oxide particles (B). From the viewpoint of embeddability, the content of the colorant (total content when two or more types are included) is preferably 0.1 to 30 mass %, and more preferably 0.5 to 25 mass %, based on the total amount (100 mass %) of the resin composition layer.
[0104] The surface conditioning additive may be a surfactant that does not contain a radical polymerizable group and has a weight average molecular weight (Mw) of 1,000 to 9,999, such as a silicone-based, silicone acrylic-based, fluorine-based, or acetylene glycol-based surfactant. Among these, from the viewpoint of adhesion, it is particularly preferable to contain a silicone-based or silicone acrylic-based surfactant. The silicon-based surface conditioning additive is preferably, for example, a modified polysiloxane compound in which an organic group is introduced into a part of the methyl group of polydimethylsiloxane. Examples of modification include polyether modification, methylstyrene modification, alcohol modification, alkyl modification, aralkyl modification, fatty acid ester modification, epoxy modification, amine modification, amino modification, and mercapto modification, but are not particularly limited thereto. These modification methods can be used in combination. Among them, polyether modified polysiloxane compounds and aralkyl modified polysiloxane compounds are preferred in terms of compatibility and the like. From the viewpoint of coating suitability, the content of the surface conditioning additive is preferably 0.01 to 10 mass %, and more preferably 0.1 to 5 mass %, based on the total amount (100 mass %) of the resin composition layer.
[0105] The adhesion improver may be an oligomer having a weight average molecular weight (Mw) of 1,000 to 9,999 that does not contain a radical polymerizable group. Examples of the adhesion improver include rosin resins, terpene resins, alicyclic petroleum resins, and aromatic petroleum resins. The weight average molecular weight (Mw) of the adhesion improver is more preferably 2,000 to 8,000, and further preferably 3,000 to 5,000. From the viewpoint of adhesion, the content of the adhesion improver is preferably 0.1 to 20 mass %, and more preferably 1 to 15 mass %, based on the total amount (100 mass %) of the resin composition layer. EXAMPLES
[0106] The present disclosure will be specifically described below with reference to examples and comparative examples, but the present disclosure is not particularly limited to the examples. In the following description, "parts" and "%" represent "parts by mass" and "% by mass", respectively, unless otherwise specified.
[0107] The values obtained in this example were obtained by the following method. [Glass transition temperature (Tg) of resin (A)] The coating solution of resin (A) was applied onto the release layer of a 75 μm-thick protective film (Mitsui Chemicals Tohcello, SP-PET-O3) so that the thickness after drying would be 20 μm. After drying for 3 minutes in a hot air oven at 100°C, a 50 μm-thick release liner (Mitsui Chemicals The release layer side of SP-PET-O1 (manufactured by Tocello Co., Ltd.) was attached. The protective film and release liner were then peeled off, and the Tg of the resulting resin (A) was measured using a differential scanning calorimeter (manufactured by TA Instruments, "Discovery DSC 2500"). Approximately 2 mg of the sample was placed in an aluminum pan, weighed, and set in the differential scanning calorimeter. The same type of aluminum pan without the sample was used as a reference, and the sample was held at 100°C for 5 minutes, and then rapidly cooled to -50°C using liquid nitrogen. The temperature was then increased at a rate of 5°C / min, and the glass transition temperature (Tg) of the resin (A) was determined from the obtained DSC chart.
[0108] [Weight average molecular weight (Mw) and number average molecular weight (Mn)] The weight average molecular weight (Mw) and number average molecular weight (Mn) were measured using a GPC "LC-GPC system" manufactured by Shimadzu Corporation, and the weight average molecular weight (Mw) and number average molecular weight (Mn) were calculated by conversion using polystyrene with a known molecular weight as a standard substance. Device name: Shimadzu Corporation, LC-GPC system "Prominence" Column: Four GMHXL columns manufactured by Tosoh Corporation and one HXL-H column manufactured by Tosoh Corporation were connected together. Mobile phase solvent: Tetrahydrofuran Flow rate: 1.0mL / min Column temperature: 40℃
[0109] [Solid content] The mass of the aluminum cup (W0) was measured using a precision balance. Next, about 1 g of sample was placed in the aluminum cup, and the mass of the sample in the aluminum cup (W1) was measured using a precision balance. The sample in the aluminum cup was heated in an oven at 150°C for 120 minutes, then removed from the oven and returned to room temperature. The residual mass (W2) of the sample in the aluminum cup after heating was measured using a precision balance. The solid content was then calculated using the formula (W2-W0) / (W1-W0)×100(%).
[0110] [Acid value] The "acid value" herein refers to the acid value per 1 g of solid content of resin (A), and was determined by potentiometric titration in accordance with JIS K 0070.
[0111] [Production example of resin (A)] [Production Example of (Meth)acrylic Resin (a) (R-1)] A reaction vessel (hereinafter simply referred to as "reaction vessel") equipped with a stirrer, a thermometer, a reflux condenser, a dropping device, and a nitrogen inlet tube was charged with 80 parts of ethyl acetate, 20 parts of methyl methacrylate, 79 parts of n-butyl methacrylate, 1 part of methacrylic acid, and 0.1 parts of 2,2'-azobisisobutyronitrile as an initiator, and the atmosphere in the reaction vessel was replaced with nitrogen gas. Then, the mixture was heated to 65°C while stirring under a nitrogen atmosphere to start the reaction. The reaction solution was then reacted at 65°C for 4 hours. After the reaction was completed, the mixture was cooled and diluted with ethyl acetate to obtain a solution of acrylic resin (R-1) with a weight average molecular weight (Mw): 35,000, a dispersity (Mw / Mn): 2, a glass transition temperature (Tg): 35°C, an acid value: 7 mgKOH / g, and a solid content: 25%.
[0112] [Production Examples of (Meth)acrylic Resins (a) (R-2 to R-4)] (Meth)acrylic resins (a) (R-2 to R-4) were produced in the same manner as for the production of (meth)acrylic resin (a) (R-1), except that the compositions and blending amounts (parts by mass) were changed to those shown in Table 1. Note that blanks indicate that no blend was used, and the solid content was 25% in all cases.
[0113] [Table 1]
[0114] The abbreviations in the table are as follows. BA: n-butyl acrylate MMA: Methyl methacrylate nBMA: n-butyl methacrylate MAA: Methacrylic acid 2HEMA: 2-hydroxyethyl methacrylate GMA: glycidyl methacrylate MOI: 2-Methacryloyloxyethyl isocyanate
[0115] [Production example of urethane resin (R-5)] A glass flask equipped with a stirrer, a thermometer, a reflux condenser, a nitrogen inlet tube, and a pressure reducing device was charged with 166 parts of terephthalic acid, 146 parts of adipic acid, 212 parts of 3-methyl-1,5-pentanediol, and 25 parts of ethylene glycol, and stirred while passing nitrogen gas through it. The temperature was gradually raised under normal pressure, and the mixture was reacted at 200 to 230°C for about 8 hours to obtain a liquid with an acid value of 43 mgKOH / g. Then, 0.01 parts of tetra-n-butoxytitanium was charged, and after nitrogen replacement, the mixture was stirred at 180°C for 30 minutes under a sealed condition. Then, the mixture was reacted at 230°C and 5 mmHg for 2 hours to obtain a polyester diol with an acid value of 1.1 mgKOH / g, a hydroxyl value of 114.2 mgKOH / g, a weight average molecular weight (Mw): 982, and a hue of 10 (APHA method, the same below). Next, 734 parts of the polyester diol, 23.9 parts of dimethylolpropionic acid, 219 parts of toluene diisocyanate, and 242 parts of toluene were charged into a reaction vessel equipped with a stirrer, a thermometer, a reflux condenser, a dropping device, and a nitrogen inlet tube, and reacted for 8 hours at 50° C. under a nitrogen atmosphere. 1200 parts of toluene were added to this to obtain a solution of a urethane prepolymer having an isocyanate group at its terminal. Next, the obtained prepolymer solution was heated to 70° C. and, while maintaining the temperature, 20.0 parts of 1,3-diaminopropane, 3.1 parts of benzylamine, 600 parts of 2-propanol, A solution containing 961 parts of toluene was added dropwise over 1 hour. After the completion of the addition, the mixture was allowed to react for an additional 6 hours at 70°C, yielding a solution of urethane resin (R-5) with a weight average molecular weight (Mw): 150,000, a degree of dispersion (Mw / Mn): 4.5, a glass transition temperature (Tg): 18°C, an acid value: 10 mgKOH / g, and a solid content: 25%.
[0116] [Example of manufacturing a dispersion of metal oxide particles (B)] [Dispersant manufacturing example] In a four-neck flask equipped with a stirrer, reflux condenser, gas inlet tube, and thermometer, 60.0 parts of isomyristyl alcohol, 127.8 parts of ε-caprolactone, 112.2 parts of δ-valerolactone, and 0.1 parts of monobutyltin (IV) oxide as a catalyst were charged, and after replacing with nitrogen gas, the mixture was reacted at 120 ° C. for 3 hours while stirring. After confirming that 98% had reacted by solid content measurement, 30.5 parts of pyromellitic dianhydride were added and reacted at 100 ° C. for 5 hours. After the reaction was completed, the mixture was cooled and the solid content was adjusted with methyl ethyl ketone to obtain a dispersant with a solid content of 81%, an acid value of 49 mg KOH / g, and a linear, acidic dispersant.
[0117] [Production Example of Dispersion (D-1) of Metal Oxide Particles (B)] Metal oxide particles (B) were ZrO2 (PCS60, manufactured by Shin-Nihon Denko Co., Ltd., number-average primary particle diameter 20 nm, specific surface area by BET method 50-70 m 2 724 parts of 1,2-dichlorophenyl ether (1 / g), 80.2 parts of the above-mentioned dispersant, and 1195.8 parts of methyl ethyl ketone were mixed and pre-dispersed using a disperser, after which main dispersion was carried out for 2 hours using a 0.6 L Dyno Mill filled with 1800 g of zirconia beads with a diameter of 0.3 mm. After dispersion was completed, the zirconia beads were removed to obtain a dispersion (D-1) of metal oxide particles (B) with a solid content of 39.4% and a concentration of metal oxide particles (B) of 36.2%. [Production Example of Dispersion (D-2) of Metal Oxide Particles (B)] Metal oxide particles (B) were TiO2 (MT-05, manufactured by Teika Co., Ltd., number-average primary particle diameter 10 nm, specific surface area by BET method 20 to 50 m 2 A dispersion (D-2) of metal oxide particles (B) having a solid content of 39.4% and a concentration of metal oxide particles (B) of 36.2% was produced in the same manner as in the production of the dispersion (D-1) of metal oxide particles (B), except that the dispersion was changed to DISPERBYK (registered trademark)-180 (manufactured by BYK-Chemie, solid content 81%) and the dispersant was changed to DISPERBYK (registered trademark)-180 (manufactured by BYK-Chemie, solid content 81%). [Production Example of Dispersion (D-3) of Metal Oxide Particles (B)] Metal oxide particles (B) were SiO2 (AEROSIL (registered trademark) 50, manufactured by Nippon Aerosil Co., Ltd., number average primary particle diameter 50 nm, specific surface area by BET method 35 to 65 m 2 A dispersion (D-3) of metal oxide particles (B) having a solid content of 39.4% and a metal oxide particle (B) concentration of 36.2% was produced in the same manner as in the production of the dispersion (D-1) of metal oxide particles (B), except that the mixing ratio of the dispersion (D-1) was changed to 1:1 / g. [Production Example of Dispersion (D-4) of Metal Oxide Particles (B)] Metal oxide particles (B) were Al2O3 (AEROXIDE (registered trademark) Alu C, manufactured by Nippon Aerosil Co., Ltd., number-average primary particle diameter: 13 nm, specific surface area by BET method: 85 to 115 m 2 A dispersion (D-4) of metal oxide particles (B) having a solid content of 39.4% and a metal oxide particle (B) concentration of 36.2% was produced in the same manner as in the production of the dispersion (D-1) of metal oxide particles (B), except that the mixing ratio of the dispersion (D-1) was changed to 1:1 / g. [Production Example of Dispersion (D-5) of Metal Oxide Particles (B)] Metal oxide particles (B) were TiO2 (MT-700B, manufactured by Teika Co., Ltd., number average primary particle diameter 80 nm, specific surface area by BET method 20 to 60 m 2 A dispersion (D-5) of metal oxide particles (B) having a solid content of 39.4% and a metal oxide particle (B) concentration of 36.2% was produced in the same manner as in the production of the dispersion (D-1) of metal oxide particles (B), except that the mixing ratio of the dispersion (D-1) was changed to 1:1.
[0118] [Example 1] [Production of resin composition] As the resin (A), the above-mentioned (meth)acrylic resin (a) (R-1) solution: 314.8 parts (resin (A) 78.7 parts, solvent 236.1 parts), the dispersion (D-1) of metal oxide particles (B): 41.4 parts (solid content 16.3 parts (including metal oxide particles (B) 15 parts), solvent 25.1 parts), the epoxy-based crosslinking agent jER (registered trademark) YX8034 (manufactured by Mitsubishi Chemical Corporation): 5 parts as a crosslinking agent as other components, and methyl ethyl ketone: 55 parts as a solvent were sequentially added while stirring with a disperser, and stirred until sufficiently uniform. Next, filtration was performed with a membrane filter with a pore size of 10 μm to remove coarse foreign matter that would cause coating unevenness, and a resin composition with a solid content of 24% was obtained. The amounts of the resin (A), metal oxide particles (B), crosslinking agent and other components shown in Table 2 are calculated as solid contents.
[0119] [Manufacturing of encapsulating sheets] The resin composition was applied onto the release layer of a 38 μm-thick protective film (Mitsui Chemicals Tohcello, SP-PET-O3; Sq on the release layer side is 0.3 μm) so that the thickness after drying was 20 μm, and the resin composition layer was formed by drying for 3 minutes in a hot air oven at 100° C. Next, the release layer side of a 50 μm-thick release liner (Mitsui Chemicals Tohcello, SP-PET-O1) was attached to the exposed resin composition layer, and aged at 0° C. for 7 days to obtain an encapsulating sheet of Example 1 in which the protective film / 20 μm-thick resin composition layer / release liner were laminated in this order.
[0120] [Thickness of encapsulating sheet Tt, thickness of resin composition layer Ta, thickness of protective film Tb, thickness of release liner Tc] Ten equally spaced points were determined from one end to the other end in the width direction of the encapsulating sheet cut to a size of 10 cm x 10 cm, and the thicknesses of the ten points were measured, and the average value was taken as the thickness Tt of the encapsulating sheet. Next, the release liner was peeled off from the encapsulating sheet, and the thicknesses of the peeled release liner at the ten points corresponding to the same positions as described above were measured. The average value was taken as Tc. Thereafter, the protective film was further peeled off from the resin composition layer, and the thicknesses of the peeled protective film at the ten points corresponding to the same positions as described above were measured. The average value was taken as Tb. The thickness Ta of the resin composition layer was calculated by the following (Formula 2). The thickness was measured using an MH-15M (manufactured by Nikon Corporation). Ta = Tt - Tc - Tb (Equation 2)
[0121] [Tan δ peak intensity of resin composition layer, tan δ40] An encapsulating sheet was prepared in the same manner as in the above-mentioned encapsulating sheet manufacturing example, except that the thickness of the resin composition layer was changed to 50 μm. The sheet was cut to a size of 0.5 cm × 2 cm, and the protective film and the release liner were peeled off. The dynamic viscoelasticity of the obtained resin composition layer was measured using a dynamic viscoelasticity measuring device DVA-200 / L2 (manufactured by IT Measurement and Control Co., Ltd.) at a frequency of 10 Hz, a measurement temperature range of -50 to 150 ° C., a heating rate of 5 ° C. / min, and a tensile mode, and the loss tangent (tan δ) was plotted. The peak top intensity (tan δ peak intensity) of the loss tangent (tan δ) and the loss tangent at 40 ° C. (tan δ40) were read from the obtained graph.
[0122] [Refractive index] The encapsulating sheet of Example 1 was cut into a size of 2 cm x 5 cm, and the protective film and the release liner were peeled off. The refractive index of the obtained resin composition layer was measured using an Abbe refractometer (DR-M2, Atago Co., Ltd.).
[0123] [Haze / total light transmittance] The encapsulating sheet of Example 1 was cut to a size of 2.5 cm x 10 cm, and a glass plate (blue plate glass, manufactured by Kawamura Kyuzo Shoten Co., Ltd.) having a thickness of 1.1 mm was attached to the surface from which the release liner was removed, and then a protective sheet was applied. The film was peeled off. The haze value and total light transmittance of the resin composition layer were measured using a haze meter (NDH8000, manufactured by Nippon Denshoku Industries Co., Ltd.).
[0124] [Saturation C * ] The sealing sheet of Example 1 was cut to a size of 2.5 cm x 10 cm, and a glass plate (blue plate glass, manufactured by Kawamura Kuzo Shoten Co., Ltd.) having a thickness of 1.1 mm was attached to the surface from which the release liner was removed, and then the sheet was left to stand for 120 minutes under a condition of 180°C. The glass plate was placed on a standard white plate so as to be in contact with the standard white plate, and the protective film was peeled off to produce a standard white plate / glass plate / resin composition layer configuration. A colorimeter (X-Rite eXact, manufactured by X-Rite Co., Ltd.) was used to measure the color of the sample under the light source conditions of D50 / 2°. * Value and b * The value was measured at three arbitrary points on the surface of the resin composition layer, and the average value was calculated. * The average value and b * Average value of saturation C * was calculated. C * =(a *2 +b *2 ) 0.5 (Formula 1)
[0125] [Root mean square height Sq] The peelable layer surface of the protective film cut to a size of 10 cm x 10 cm was measured at any five points using a confocal microscope (Lasertec, OPTELICS HYBRID+, objective lens 20x) in accordance with ISO 25178, and the data was then analyzed using data analysis software (LMeye8) to calculate the peelability.
[0126] [Evaluation method and criteria] [Embeddability] A test substrate was prepared that mimicked the unevenness of a micro LED substrate (a glass plate measuring 25 mm × 25 mm, with recesses 200 μm wide, protrusions 5 μm high, and protrusions 200 μm wide formed on one side). A schematic cross-sectional view of the test substrate is shown in Figure 3. The sealing sheet was cut to a size of 30 mm x 30 mm, the release liner was peeled off to expose the resin composition layer, and the resin composition layer was placed on the surface of the test substrate on which the uneven portion was formed. Thereafter, a 50 μm thick TPX (Opulant X-44B, manufactured by Mitsui Chemicals Tocello Co., Ltd.) and a 2.0 mm thick PVC film (Celeb T, manufactured by Okamoto Co., Ltd.) were laminated in order on the protective film as cushioning materials, and cardboard was further laminated to prevent sticking. A laminate consisting of a glass substrate / resin composition layer / protective film / cushioning material (TPX / PVC film) / cardboard was pressed from above against the substrate surface at 5 MPa and 100° C. for 20 minutes, and the resin composition layer was filled in the recesses of the test substrate to form a sealing layer. After pressing, the cushioning material and the cardboard were peeled off. The sealing layer protruding from the side of the obtained test substrate with sealing layer was roughly removed using a cutter, and further the sealing layer remaining on the side of the test substrate with sealing layer was removed by sanding, exposing the side of the test substrate so that the uneven parts could be observed. The embeddability was evaluated by observing the recesses of 15 randomly selected test substrates with a microscope. In the recesses of the test substrate, the grooves were deemed to be embedded when the maximum gap between the sealing layer and the test substrate was 1 μm or less. The evaluation criteria were as follows, with A to C being considered good, and a rating of D being given for failure to achieve the target performance. A: 14 or more recessed grooves B: 13 or less recessed grooves, 11 or more recessed grooves C: 10 or less recessed grooves, 8 or more recessed grooves D: 7 or fewer recessed grooves
[0127] [Seamlessness] One sheet of the sealing sheet of Example 1 was prepared by cutting it to 25 mm × 100 mm, the release liner was peeled off to expose the resin composition layer, and the sheet was placed on a glass plate (25 mm × 100 mm × 1.1 mm, blue plate glass, manufactured by Kawamura Kuzo Shoten Co., Ltd.) so that the ends were aligned. Then, a 50 μm-thick TPX (Opulent X-44B, Mitsui A 2.0 mm thick PVC film (Celeb T, manufactured by Okamoto Corporation) was laminated in this order, and cardboard was further laminated to prevent sticking. The laminate consisting of glass plate / resin composition layer / protective film / cushion material (TPX / PVC film) / cardboard was pressed from above against the substrate surface at 5 MPa and 100°C for 20 minutes to pressure-bond the glass plate and the resin composition layer, forming a sealing layer on the glass plate. After pressing, the cushion material and cardboard were peeled off to obtain a seamless test piece. The protective film was peeled off from the obtained seamless test piece, and the haze (Hs) was measured. Next, two pieces of the sealing sheet were prepared by cutting into a size of 25 mm in length and 50 mm in width, and the release film was peeled off to expose the resin composition layer, and the ends were aligned side by side on a glass plate (25 mm x 100 mm x 1.1 mm, blue plate glass, manufactured by Kawamura Kuzo Shoten Co., Ltd.). Thereafter, the pieces were pressed in the same manner as the seamless test piece to obtain a joint test piece in which the interface between the sealing layers formed from the two sealing sheets was the joint. The protective film was peeled off from the joint test piece, and the haze (Hj) of the joint area was measured. The change in haze between the seamless specimen (Hs) and the joint specimen (Hj) (|Hs-Hj| / 100(%)) was calculated and evaluated. The evaluation criteria were as follows, with A to C being considered good, and a rating of D being given for failure to achieve the target performance. A: Change is 0.5% or less B: The change is greater than 0.5% and less than 0.8% C: The change is greater than 0.8% and less than 1.0% D: The change is greater than 1.0%
[0128] [Adhesion] A seamless test specimen used for seamlessness evaluation was prepared, the protective film was peeled off, and the test specimen consisting of a glass plate and a sealing layer was left to stand at 180°C for 120 minutes to produce a test specimen in which the glass plate and the sealing layer were tightly adhered to each other. According to JIS K 5600-5-6 (cross-cut method), a lattice pattern (25 squares) of 1 mm squares was created on the sealing layer of the test piece using a cross-cut guide and a cutter knife, and adhesive tape (CT1835, Nichiban Co., Ltd.) was attached to the lattice-cut area and firmly adhered to the sealing layer. Within 5 minutes of adhesion, the tape was pulled off at an angle close to 60° in 0.5 to 1.0 seconds. The appearance of the peeled sealing layer was observed to evaluate adhesion. The evaluation criteria were as follows, with A to C being considered good, and a rating of D being given for failure to achieve the target performance. A: 0 pieces completely peeled off, only the edge of the cut had no partial peeling B: No masses were completely peeled off, and only the edge of the cut had partial peeling. C: 1 to 2 peeled squares D: 3 or more peeled squares
[0129] [Visibility] A seamless test specimen used for seamlessness evaluation was prepared, the protective film was peeled off, and the test specimen consisting of a glass plate and a sealing layer was left to stand at 180°C for 120 minutes to produce a test specimen in which the glass plate and the sealing layer were tightly adhered to each other. The test piece was placed on an LED display device (LED Name Badge (white), manufactured by Asco) so that the sealing layer was in contact with the display surface, creating a laminate consisting of a display device / sealing layer / glass plate. Next, white letters (a total of three letters, capital letters A to C) were displayed on a black background on the display device. An observer observed the displayed letters from two angles: an angle of 30° from the horizontal and a vertical angle of 90°. The observer visually compared and evaluated the distortion of the displayed letters and the blurring of the outlines before and after placing the test piece. The evaluation criteria were as follows, with A to B being considered good and D being given as not achieving the target performance. A: No distortion or blurring of the edges is observed under any angle conditions. B: Distortion and / or blurring of the outline is observed under any one of the angle conditions. D: Distortion and / or blurring of edges is observed under all angle conditions.
[0130] [Examples 2 to 37], [Comparative Examples 1 to 10] The sealing sheets were prepared and evaluated in the same manner as in Example 1, except that the contents, thicknesses Ta, and protective films were changed to those shown in Tables 2 to 5. Note that any crosslinking agents, oligomers, monomers, polymerization initiators, and other components were added at the same time. In Tables 2 to 5, the amounts of resin (A), crosslinking agent, oligomer, monomer, polymerization initiator, and other components are calculated as solid content. The amount of metal oxide particles (B) is calculated as the solid content of the dispersions (D-1 to D-5) and the amount of metal oxide particles (B) in the dispersions (D-1 to D-5) is shown in parentheses. Blanks indicate that no compound was added.
[0131] The abbreviations in the table are as follows. C-1: Epoxy crosslinking agent (jER (registered trademark) YX8034, hydrogenated bisphenol A type epoxy resin, manufactured by Mitsubishi Chemical Corporation) C-2: Isocyanate compound (Cosmonate (registered trademark) T100, 2,4-tolylene diisocyanate, manufactured by Mitsui Fine Chemicals, Inc.) C-3: Silane coupling agent (KBE-403, 3-glycidoxypropyltrimethoxysilane, manufactured by Shin-Etsu Silicone Co., Ltd.) O-1: Urethane acrylate oligomer (KRM8667, Daicel Allnex Corporation, trifunctional, weight average molecular weight 2000, viscosity at 60°C 11,000cps) O-2: Epoxy acrylate oligomer (Miramer (registered trademark) HR6042, manufactured by MIWON, bifunctional, weight average molecular weight 1400, viscosity at 25°C 21,000 cps) O-3: Polyester acrylate oligomer (Miramer (registered trademark) PS4040, manufactured by MIWON, 4-functional, weight average molecular weight 1300, viscosity at 25°C 6,300 cps) O-4: Acrylic ester oligomer (ART CURE (registered trademark) UN-9000PEP, manufactured by Negami Chemical Industries, 2-functional, weight average molecular weight 5000, viscosity at 25°C 2,000,000 cps) M-1: EO-modified (3) trimethylolpropane triacrylate (Miramer (registered trademark) M3130, manufactured by MIWON, trifunctional, viscosity at 25°C 65 cps) M-2: 1,6-hexanediol diacrylate (Viscoat (registered trademark) #230, manufactured by Osaka Organic Chemical Industry Co., Ltd., bifunctional, viscosity at 25°C 7 cps) I-1: Di-t-butyl peroxide (Perbutyl (registered trademark) D, NOF Corporation) I-2: 2,2'-azobis(N-butyl-2-methylpropionamide) (VAm-110, Fujifilm Wako Pure Chemical Industries, Ltd.) A-1: Phosphorus-based antioxidant (ADEKA STAB PEP-36, manufactured by ADEKA Corporation) A-2: Surface conditioner (BYK (registered trademark)-3440, manufactured by BYK-Chemie) P-1: 38 μm thick protective film (SP-PET-O3, manufactured by Mitsui Chemicals Tocello, Sq: 0.3 μm) P-2: 75 μm thick protective film (matte film (type M3), manufactured by Aim Co., Ltd., Sq: 1.5 μm) P-3: 50μm thick protective film (matte film (type M8), manufactured by Aim Co., Ltd., Sq: 1.0μm) P-4: 10 μm thick protective film (matte film (type M3), manufactured by Aim Co., Ltd., Sq: 1.5 μm) P-5: 100 μm thick protective film (matte film (type M8), manufactured by Aim Co., Ltd., Sq: 1.0 μm) P-6: 188μm thick protective film (matte film (type M3), manufactured by Aim Co., Ltd., Sq: 1.5μm) P-7: 200 μm thick protective film (matte film (type M2), manufactured by Aim Co., Ltd., Sq: 2.0 μm)
[0132] [Table 2]
[0133] [Table 3]
[0134] [Table 4]
[0135] [Table 5]
[0136] In the present disclosure, in the case of a sealing sheet that does not contain metal oxide particles (B) having a number-average primary particle diameter of 5 to 50 nm, it is found that there are problems with embedding property, adhesion, or visibility, as shown in Comparative Examples 1, 5, 6, and 10. In addition, in the case of a sealing sheet having a refractive index outside the range of 1.45 to 1.65, there are problems with seamlessness and visibility, as shown in Comparative Examples 2 to 4 and 7 to 9. There is. The encapsulating sheets of Comparative Examples 1 to 10 were unable to achieve a balanced and satisfactory high level of embeddability and seamlessness, and were also unable to achieve a satisfactory high level of adhesion and visibility. In contrast, according to Examples 1 to 37, the encapsulating sheet of the present disclosure exhibits excellent embedding properties and is also excellent in seamlessness as shown in Tables 2 to 5. Furthermore, since the encapsulating sheet of the present disclosure is also excellent in adhesion and visibility, it was found that the encapsulating sheet of the present disclosure can be suitably used for encapsulating an optical semiconductor element. [Explanation of symbols]
[0137] 1: Encapsulating sheet 2: Resin composition layer 2´: Sealing layer 3: Base material 4: Release liner 5: Optical semiconductor elements 6: Substrate 7: Glass substrate
Claims
1. An encapsulating sheet for encapsulating an optical semiconductor element, The encapsulating sheet has a protective film and a resin composition layer arranged in this order, The resin composition layer contains a resin (A) and metal oxide particles (B), The metal oxide particles (B) have a number average primary particle diameter of 5 to 50 nm, The encapsulating sheet, wherein the resin composition layer has a refractive index of 1.45 to 1.
65.
2. The encapsulating sheet according to claim 1 , wherein the metal oxide particles (B) contain at least one selected from the group consisting of Ti, Al, and Zr.
3. The encapsulating sheet according to claim 1 , wherein the resin (A) comprises at least one resin selected from the group consisting of a (meth)acrylic resin (a) and a urethane resin (b).
4. The resin composition layer has a haze of 12% or less and a total light transmittance of 80% or more, CIE L of the resin composition layer * a * b * Saturation C determined from color space * The encapsulating sheet according to claim 1, wherein the Mn content is 0 to 10.
5. The resin composition layer has a thickness Ta of 1 to 100 μm, The encapsulating sheet according to claim 1, wherein the protective film has a thickness Tb of 10 to 188 μm.
6. the protective film and the resin composition layer are directly laminated together, The ratio of the root mean square height Sq defined in ISO 25178 on the surface of the protective film in contact with the resin composition layer to the thickness Ta of the resin composition layer is 0.01 to 30%. The encapsulating sheet according to claim 5.
7. The encapsulating sheet according to any one of claims 1 to 6, wherein the loss tangent of the resin composition layer obtained by dynamic viscoelasticity measurement in the range of -50 to 80 ° C. has a peak top strength (tan δ peak strength) of 0.6 to 2.
2.
8. The encapsulating sheet according to claim 7 , wherein the optical semiconductor element is a micro LED.
9. A display having a sealing layer containing a resin (A) and metal oxide particles (B), the metal oxide particles (B) having a number average primary particle diameter of 5 to 50 nm and a refractive index of 1.45 to 1.65.
Citation Information
Patent Citations
Optical semiconductor device sealing sheet
WO2021200035A1